Pressure-sensitive adhesive composition, pressure-sensitive adhesive sheet, optical laminate, and image display device
A pressure-sensitive adhesive composition with (meth)acrylic polymer, isocyanate crosslinking agent, polyhydroxyalkylamine, and polyether compound addresses dimensional changes in optical films, enhancing reworkability and optical performance in image display devices.
Patent Information
- Application Number
- JP2022184943
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-11-18
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-11-18
AI Technical Summary
Excessive dimensional changes in optical films due to temperature variations cause light leakage and color unevenness in image display devices, particularly in those with narrow frames, leading to issues with adhesive strength and reworkability.
A pressure-sensitive adhesive composition combining (meth)acrylic polymer, isocyanate crosslinking agent, polyhydroxyalkylamine compound, and polyether compound to enhance reworkability while maintaining sufficient adhesive strength.
The composition improves reworkability by reducing adhesive force variation with temperature, preventing stress concentration and interlayer separation, and maintaining optical performance in image display devices.
Smart Images

Figure 0007612644000010 
Figure 0007612644000011 
Figure 0007612644000012
Abstract
Description
[Technical field]
[0001] The present invention relates to a pressure-sensitive adhesive composition, a pressure-sensitive adhesive sheet, an optical laminate, and an image display device. [Background technology]
[0002] In recent years, image display devices such as liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices and inorganic EL display devices) have rapidly become widespread. These various image display devices usually have a laminated structure of an image forming layer such as a liquid crystal layer and an EL light emitting layer, and an optical laminate including an optical film and an adhesive sheet. The adhesive sheet is mainly used for bonding between films included in the optical laminate, or for bonding between the image forming layer and the optical laminate. Examples of optical films are a polarizing film, a retardation film, and a polarizing film with a retardation film in which a polarizing film and a retardation film are integrated. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2008-096734 A Summary of the Invention [Problem to be solved by the invention]
[0004] Excessive changes in the dimensions of the optical film due to temperature changes cause light leakage and color unevenness in image display devices. In particular, image display devices designed with narrow bezels (narrowed bezels) are becoming more and more popular, and suppressing changes in dimensions is becoming increasingly important. In order to suppress changes in dimensions, it is considered to increase the elastic modulus of the adhesive sheet contained in the optical laminate. As a method for increasing the elastic modulus of the adhesive sheet, an increase in the amount of crosslinking agent in the adhesive composition for producing the adhesive sheet can be mentioned. For example, Patent Document 1 discloses an adhesive composition using a sufficient amount of an isocyanate-based crosslinking agent.
[0005] However, according to the study by the present inventors, when a pressure-sensitive adhesive sheet is produced using a pressure-sensitive adhesive composition containing a sufficient amount of an isocyanate-based crosslinking agent, when an optical laminate and an adherend such as an image forming layer are bonded together via the pressure-sensitive adhesive sheet, the adhesive strength between the optical laminate and the adherend tends to increase excessively over time. In particular, the adhesive strength between the optical laminate and the adherend is likely to increase excessively under high temperature conditions. When the adhesive strength between the optical laminate and the adherend increases excessively, it becomes difficult to peel the optical laminate from the adherend, and its reworkability decreases. In particular, when a film (e.g., a retardation film) adjacent to the pressure-sensitive adhesive sheet is thin in the optical laminate, when an attempt is made to peel the optical laminate from the adherend, stress is concentrated near the film, and delamination is likely to occur within the optical laminate. When delamination occurs within the optical laminate, a part of the optical laminate will remain on the adherend.
[0006] Therefore, an object of the present invention is to provide a pressure-sensitive adhesive composition which contains a sufficient amount of an isocyanate-based crosslinking agent and is suitable for producing a pressure-sensitive adhesive sheet having improved reworkability. [Means for solving the problem]
[0007] As a result of extensive research, the present inventors have newly discovered that the reworkability of a pressure-sensitive adhesive sheet can be improved by combining a polyhydroxyalkylamine compound with a polyether compound, and have thus completed the present invention.
[0008] The present invention relates to A (meth)acrylic polymer (A), an isocyanate-based crosslinking agent in an amount of 2 parts by weight or more based on 100 parts by weight of the (meth)acrylic polymer (A); A polyhydroxyalkylamine compound, A polyether compound, The present invention provides a pressure-sensitive adhesive composition comprising:
[0009] Further, the present invention relates to A pressure-sensitive adhesive sheet formed from the above pressure-sensitive adhesive composition is provided.
[0010] Further, the present invention relates to The present invention provides an optical laminate comprising the above pressure-sensitive adhesive sheet and an optical film.
[0011] Further, the present invention relates to There is provided an image display device including the above optical laminate. Effect of the Invention
[0012] According to the present invention, it is possible to provide a pressure-sensitive adhesive composition which contains a sufficient amount of an isocyanate-based crosslinking agent and is suitable for producing a pressure-sensitive adhesive sheet having improved reworkability. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a cross-sectional view that illustrates an example of the pressure-sensitive adhesive sheet of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view that illustrates an example of the optical layered body of the present invention. [Diagram 3] FIG. 3 is a cross-sectional view that illustrates an example of the optical layered body of the present invention. [Figure 4] FIG. 4 is a cross-sectional view that illustrates an example of the optical layered body of the present invention. [Diagram 5] FIG. 5 is a cross-sectional view that illustrates an example of the optical layered body of the present invention. [Figure 6] FIG. 6 is a cross-sectional view that illustrates an example of the optical layered body of the present invention. [Figure 7] FIG. 7 is a cross-sectional view that illustrates an example of an image display device of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The pressure-sensitive adhesive composition according to the first aspect of the present invention comprises: A (meth)acrylic polymer (A), an isocyanate-based crosslinking agent in an amount of 2 parts by weight or more based on 100 parts by weight of the (meth)acrylic polymer (A); A polyhydroxyalkylamine compound, A polyether compound, Includes.
[0015] In a second aspect of the present invention, for example in the pressure-sensitive adhesive composition according to the first aspect, the polyether compound further has a silicon atom, and a hydroxyl group and / or a hydrolyzable group bonded to the silicon atom.
[0016] In a third aspect of the present invention, for example, in the pressure-sensitive adhesive composition according to the first or second aspect, the blending amount of the polyether compound is 0.1 to 5 parts by weight per 100 parts by weight of the (meth)acrylic polymer (A).
[0017] In a fourth aspect of the present invention, for example, in the pressure-sensitive adhesive composition according to any one of the first to third aspects, the polyhydroxyalkylamine compound has a molecular weight of 1,500 or less.
[0018] In a fifth aspect of the present invention, for example, in the pressure-sensitive adhesive composition according to any one of the first to fourth aspects, the blending amount of the polyhydroxyalkylamine compound is 0.01 to 5 parts by weight per 100 parts by weight of the (meth)acrylic polymer (A).
[0019] In a sixth aspect of the present invention, for example, in the pressure-sensitive adhesive composition according to any one of the first to fifth aspects, the blending amount of the isocyanate-based crosslinking agent is 13 parts by weight or less per 100 parts by weight of the (meth)acrylic polymer (A).
[0020] In a seventh aspect of the present invention, for example in the pressure-sensitive adhesive composition according to any one of the first to sixth aspects, the (meth)acrylic polymer (A) has a constituent unit derived from a carboxyl group-containing monomer.
[0021] In an eighth aspect of the present invention, for example, in the pressure-sensitive adhesive composition according to the seventh aspect, the (meth)acrylic polymer (A) has a content of the structural unit derived from the carboxyl group-containing monomer of 3 wt % or more.
[0022] In a ninth aspect of the present invention, for example in the pressure-sensitive adhesive composition according to any one of the first to eighth aspects, the (meth)acrylic polymer (A) has a constituent unit derived from an aromatic ring-containing monomer.
[0023] In a tenth aspect of the present invention, for example, in the pressure-sensitive adhesive composition according to any one of the first to ninth aspects, the (meth)acrylic polymer (A) has a weight average molecular weight of 1,000,000 or more.
[0024] In an eleventh aspect of the present invention, for example, in the pressure-sensitive adhesive composition according to any one of the first to tenth aspects, the isocyanate-based crosslinking agent is a tolylene diisocyanate-based crosslinking agent.
[0025] In a twelfth aspect of the present invention, for example, the pressure-sensitive adhesive composition according to any one of the first to eleventh aspects further contains a silane coupling agent.
[0026] The pressure-sensitive adhesive sheet according to a thirteenth aspect of the present invention comprises: It is formed from the pressure-sensitive adhesive composition according to any one of the first to twelfth aspects.
[0027] The optical laminate according to the fourteenth aspect of the present invention is The adhesive sheet according to the thirteenth embodiment and an optical film.
[0028] In a fifteenth aspect of the present invention, for example, the optical laminate according to the fourteenth aspect has a polarizing film, a first retardation film, and a second retardation film as the optical films.
[0029] In a sixteenth aspect of the present invention, for example, in the optical laminate according to the fifteenth aspect, the pressure-sensitive adhesive sheet is in contact with the second retardation film, and the second retardation film has a thickness of 5 μm or less.
[0030] An image display device according to a seventeenth aspect of the present invention comprises: The optical laminate according to any one of the fourteenth to sixteenth aspects is provided.
[0031] The present invention will be described in detail below, but the present invention is not limited to the following embodiments and can be modified in any manner without departing from the gist of the present invention.
[0032] (Embodiments of Pressure-Sensitive Adhesive Composition) The pressure-sensitive adhesive composition of the present embodiment includes a (meth)acrylic polymer (A), an isocyanate-based crosslinking agent in an amount of 2 parts by weight or more per 100 parts by weight of the (meth)acrylic polymer (A), a polyhydroxyalkylamine-based compound, and a polyether-based compound. A pressure-sensitive adhesive sheet can be produced from the pressure-sensitive adhesive composition.
[0033] [(Meth)acrylic polymer (A)] The (meth)acrylic polymer (A) can function as a base polymer for an acrylic pressure-sensitive adhesive. Acrylic pressure-sensitive adhesives tend to have excellent optical transparency, appropriate adhesive properties such as wettability, cohesiveness, and adhesiveness, and excellent weather resistance, heat resistance, and the like. The (meth)acrylic polymer (A) contains, for example, a structural unit derived from an alkyl (meth)acrylate as a main component. In this specification, "(meth)acrylate" means acrylate and / or methacrylate. "Main component" means a structural unit that is contained in the largest amount by weight among all structural units that constitute a polymer.
[0034] The number of carbon atoms of the alkyl group contained in the alkyl (meth)acrylate for forming the main skeleton of the (meth)acrylic polymer (A) is not particularly limited, and is, for example, 1 to 30. The alkyl group may be linear, branched, or cyclic. Examples of the alkyl group include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, an amyl group, a hexyl group, a cyclohexyl group, a heptyl group, a 2-ethylhexyl group, an isooctyl group, a nonyl group, a decyl group, an isodecyl group, a dodecyl group, an isomyristyl group, a lauryl group, a tridecyl group, a pentadecyl group, a hexadecyl group, a heptadecyl group, and an octadecyl group. The alkyl (meth)acrylates may be used alone or in combination. The average number of carbon atoms of the alkyl group is preferably 3 to 9. The alkyl (meth)acrylate is preferably butyl acrylate.
[0035] In the (meth)acrylic polymer (A), the content of structural units derived from alkyl (meth)acrylate is, from the viewpoint of improving the adhesiveness of the pressure-sensitive adhesive sheet, for example, 50% by weight or more, preferably 60% by weight or more, more preferably 70% by weight or more, and even more preferably 80% by weight or more.
[0036] Examples of monomers constituting the (meth)acrylic polymer (A) include, in addition to alkyl (meth)acrylates, at least one copolymerizable monomer selected from the group consisting of aromatic ring-containing monomers, amide group-containing monomers, carboxyl group-containing monomers, and hydroxyl group-containing monomers. The copolymerizable monomers can be used alone or in combination.
[0037] The (meth)acrylic polymer (A) preferably contains a structural unit derived from a carboxyl group-containing monomer. The carboxyl group-containing monomer is a compound that contains a carboxyl group in its structure and a polymerizable unsaturated double bond such as a (meth)acryloyl group or a vinyl group. Examples of the carboxyl group-containing monomer include (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid. Among these, acrylic acid is preferred from the viewpoints of copolymerizability, cost, and improving the adhesive properties of the adhesive sheet.
[0038] The (meth)acrylic polymer (A) has a structural unit derived from a carboxyl group-containing monomer, particularly acrylic acid, and thus, for example, the self-polymerization of an isocyanate-based crosslinking agent can be enhanced. In particular, the (meth)acrylic polymer (A) containing a structural unit derived from a carboxyl group-containing monomer tends to promote the reaction between isocyanate-based crosslinking agents by incorporating water molecules in the surrounding atmosphere. The improvement in the self-polymerization of the isocyanate-based crosslinking agent can contribute to suppression of peeling of the pressure-sensitive adhesive sheet, particularly in a humid environment, and stabilization of the physical properties of the pressure-sensitive adhesive sheet in a system with a high content of isocyanate-based crosslinking agent. Furthermore, in the (meth)acrylic polymer (A) having a structural unit derived from a carboxyl group-containing monomer, the crosslinking reaction with the crosslinking agent tends to proceed quickly due to aging. This (meth)acrylic polymer (A) is suitable for improving the reworkability of the pressure-sensitive adhesive sheet.
[0039] The (meth)acrylic polymer (A) preferably contains a structural unit derived from an aromatic ring-containing monomer. The aromatic ring-containing monomer is a compound that contains an aromatic ring structure in its structure and a polymerizable unsaturated double bond such as a (meth)acryloyl group or a vinyl group. Examples of the aromatic ring include a benzene ring, a naphthalene ring, and a biphenyl ring. The aromatic ring-containing monomer is preferably an aromatic ring-containing (meth)acrylate.
[0040] Examples of aromatic ring-containing (meth)acrylates include benzyl (meth)acrylate, phenyl (meth)acrylate, o-phenylphenol (meth)acrylate, phenoxy (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxypropyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, ethylene oxide-modified nonylphenol (meth)acrylate, ethylene oxide-modified cresol (meth)acrylate, phenol ethylene oxide-modified (meth)acrylate, 2-hydroxy- Examples of the acrylate include those having a benzene ring, such as 3-phenoxypropyl (meth)acrylate, methoxybenzyl (meth)acrylate, chlorobenzyl (meth)acrylate, cresyl (meth)acrylate, and polystyryl (meth)acrylate; those having a naphthalene ring, such as hydroxyethylated β-naphthol acrylate, 2-naphthoethyl (meth)acrylate, 2-naphthoxyethyl acrylate, and 2-(4-methoxy-1-naphthoxy)ethyl (meth)acrylate; and those having a biphenyl ring, such as biphenyl (meth)acrylate. Among these, from the viewpoint of improving the adhesive properties and durability of the adhesive sheet, benzyl (meth)acrylate and phenoxyethyl (meth)acrylate are preferred, and benzyl acrylate is more preferred.
[0041] The aromatic ring-containing monomer is suitable for improving the compatibility between the (meth)acrylic polymer (A) and the polymer (B) containing as a main component a structural unit derived from an isocyanate-based crosslinking agent described below, and for maintaining the transparency of the pressure-sensitive adhesive sheet. Furthermore, the aromatic ring-containing monomer is also suitable for adjusting the reworkability and adhesion of the pressure-sensitive adhesive sheet.
[0042] The (meth)acrylic polymer (A) may contain a structural unit derived from an amide group-containing monomer. The amide group-containing monomer is a compound that contains an amide group in its structure and a polymerizable unsaturated double bond such as a (meth)acryloyl group or a vinyl group. Examples of the amide group-containing monomer include acrylamide-based monomers such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropylacrylamide, N-methyl(meth)acrylamide, N-butyl(meth)acrylamide, N-hexyl(meth)acrylamide, N-methylol(meth)acrylamide, N-methylol-N-propane(meth)acrylamide, aminomethyl(meth)acrylamide, aminoethyl(meth)acrylamide, mercaptomethyl(meth)acrylamide, and mercaptoethyl(meth)acrylamide; N-acryloyl heterocyclic monomers such as N-(meth)acryloylmorpholine, N-(meth)acryloylpiperidine, and N-(meth)acryloylpyrrolidine; and N-vinyl group-containing lactam-based monomers such as N-vinylpyrrolidone and N-vinyl-ε-caprolactam. Among these, from the viewpoint of improving the durability of the pressure-sensitive adhesive sheet, N-vinyl group-containing lactam monomers are preferred.
[0043] The (meth)acrylic polymer (A) may contain a structural unit derived from a hydroxyl group-containing monomer. The hydroxyl group-containing monomer is a compound that contains a hydroxyl group in its structure and a polymerizable unsaturated double bond such as a (meth)acryloyl group or a vinyl group. Examples of the hydroxyl group-containing monomer include hydroxyl group-containing alkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxylauryl (meth)acrylate; and hydroxyl group-containing cycloalkyl (meth)acrylates such as (4-hydroxymethylcyclohexyl)-methylacrylate. Among these, 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are preferred.
[0044] In the (meth)acrylic polymer (A), the content of the structural units derived from the copolymerization monomer is not particularly limited and is, for example, 0 to 40% by weight, may be 0.1 to 30% by weight, or may be 0.1 to 20% by weight.
[0045] In the (meth)acrylic polymer (A), the content of the structural unit derived from the carboxyl group-containing monomer is not particularly limited, and is, for example, 0.1% by weight or more, preferably 1% by weight or more, 2% by weight or more, 3% by weight or more, or even 4% by weight or more. This content may be, for example, 25% by weight or less, 20% by weight or less, or even 10% by weight or less.
[0046] In the (meth)acrylic polymer (A), the content of the structural unit derived from the aromatic ring-containing monomer is not particularly limited, and is, for example, 3 to 25% by weight, more preferably 22% by weight or less, and even more preferably 20% by weight or less. This content is more preferably 8% by weight or more, and even more preferably 12% by weight or more.
[0047] In the (meth)acrylic polymer (A), the content of the structural units derived from the amide group-containing monomer is not particularly limited and is, for example, 0.1 to 10 wt %, more preferably 0.2 to 8 wt %, and even more preferably 0.6 to 6 wt %.
[0048] In the (meth)acrylic polymer (A), it is preferable that the content of structural units derived from copolymerization monomers having active hydrogens that are highly reactive with isocyanate-based crosslinking agents, such as hydroxyl-containing monomers, is low. In the (meth)acrylic polymer (A), the content of structural units derived from hydroxyl-containing monomers is, for example, 1% by weight or less, more preferably 0.5% by weight or less, and even more preferably 0.1% by weight or less. The (meth)acrylic polymer (A) may be substantially free of structural units derived from hydroxyl-containing monomers.
[0049] As the monomer component, in addition to the alkyl (meth)acrylate and the above-mentioned copolymerization monomers, other copolymerization monomers having a polymerizable functional group containing an unsaturated double bond such as a (meth)acryloyl group or a vinyl group can be used for the purpose of improving the adhesiveness and heat resistance of the pressure-sensitive adhesive sheet. The other copolymerization monomers can be used alone or in combination.
[0050] Examples of other copolymerizable monomers include acid anhydride group-containing monomers such as maleic anhydride and itaconic anhydride; caprolactone adducts of acrylic acid; sulfonic acid group-containing monomers such as allylsulfonic acid, 2-(meth)acrylamido-2-methylpropanesulfonic acid, (meth)acrylamidopropanesulfonic acid, and sulfopropyl (meth)acrylate; phosphoric acid group-containing monomers such as 2-hydroxyethyl acryloyl phosphate; aminoethyl (meth)acrylate, and N,N-dimethylaminoethyl (meth)acrylate. , t-butylaminoethyl (meth)acrylate and other alkylaminoalkyl (meth)acrylates; methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate and other alkoxyalkyl (meth)acrylates; N-(meth)acryloyloxymethylene succinimide, N-(meth)acryloyl-6-oxyhexamethylene succinimide, N-(meth)acryloyl-8-oxyoctamethylene succinimide and other succinimide monomers; N-cyclohexylmaleimide, N-isopropyl ... Maleimide monomers such as N-isopropylmaleimide, N-laurylmaleimide, and N-phenylmaleimide; itaconimide monomers such as N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, N-2-ethylhexylitaconimide, N-cyclohexylitaconimide, and N-laurylitaconimide; vinyl monomers such as vinyl acetate and vinyl propionate; cyanoacrylate monomers such as acrylonitrile and methacrylonitrile; glycidyl Epoxy group-containing (meth)acrylates such as (meth)acrylate; glycol-based (meth)acrylates such as polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, methoxyethylene glycol (meth)acrylate, and methoxypolypropylene glycol (meth)acrylate; (meth)acrylate monomers such as tetrahydrofurfuryl (meth)acrylate, fluorine (meth)acrylate, silicone (meth)acrylate, and 2-methoxyethyl acrylate;Examples of the silane monomers containing silicon atoms include 3-acryloxypropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 4-vinylbutyltrimethoxysilane, 4-vinylbutyltriethoxysilane, 8-vinyloctyltrimethoxysilane, 8-vinyloctyltriethoxysilane, 10-methacryloyloxydecyltrimethoxysilane, 10-acryloyloxydecyltrimethoxysilane, 10-methacryloyloxydecyltriethoxysilane, and 10-acryloyloxydecyltriethoxysilane.
[0051] Furthermore, examples of other copolymerizable monomers include polyfunctional monomers having two or more unsaturated double bonds, such as tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, bisphenol A diglycidyl ether di(meth)acrylate, neopentyl glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and caprolactone-modified dipentaerythritol hexa(meth)acrylate.
[0052] When other copolymerizable monomers are used as the monomer components, the content of structural units derived from the other copolymerizable monomers in the (meth)acrylic polymer (A) is preferably 10% by weight or less, more preferably 7% by weight or less, and even more preferably 5% by weight or less.
[0053] The weight average molecular weight of the (meth)acrylic polymer (A) is usually 300,000 to 4,000,000. From the viewpoint of durability, the weight average molecular weight of the (meth)acrylic polymer (A) is preferably 1,000,000 or more, and may be 1,500,000 or more. The weight average molecular weight of the (meth)acrylic polymer (A) may be 3,000,000 or less, and may be 2,000,000 or less. A weight average molecular weight of 300,000 or more is preferable from the viewpoint of heat resistance. If the weight average molecular weight is 4,000,000 or less, the adhesive sheet tends not to become hard and peeling does not occur easily. The weight average molecular weight (Mw) / number average molecular weight (Mn), which means the molecular weight distribution, is preferably 1.8 to 10, more preferably 1.8 to 7, and even more preferably 1.8 to 5. From the viewpoint of durability, the molecular weight distribution (Mw / Mn) is preferably 10 or less. The weight average molecular weight and the molecular weight distribution (Mw / Mn) are determined from values measured by GPC (gel permeation chromatography) and calculated in terms of polystyrene.
[0054] The (meth)acrylic polymer (A) can be prepared by a known polymerization method such as solution polymerization, radiation polymerization using electron beams or UV rays, or various radical polymerizations such as bulk polymerization and emulsion polymerization. The obtained (meth)acrylic polymer (A) may be any of a random copolymer, a block copolymer, a graft copolymer, and the like.
[0055] In the solution polymerization, for example, ethyl acetate, toluene, etc. are used as a polymerization solvent. The solution polymerization is usually carried out under reaction conditions of about 50 to 70° C. for about 5 to 30 hours by adding a polymerization initiator under a stream of an inert gas such as nitrogen.
[0056] The polymerization initiator, chain transfer agent, emulsifier, etc. used in the radical polymerization are not particularly limited and can be appropriately selected and used. The weight average molecular weight of the (meth)acrylic polymer (A) can be controlled by the amount of the polymerization initiator and the chain transfer agent used, the reaction conditions, etc. Therefore, the amount of the polymerization initiator and the chain transfer agent used is appropriately adjusted depending on the composition.
[0057] Examples of the polymerization initiator include azo initiators such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-amidinopropane)dihydrochloride, 2,2'-azobis[2-(5-methyl-2-imidazolin-2-yl)propane]dihydrochloride, 2,2'-azobis(2-methylpropionamidine)disulfate, 2,2'-azobis(N,N'-dimethyleneisobutylamidine), and 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine]hydrate (VA-057, manufactured by Wako Pure Chemical Industries, Ltd.); persulfates such as potassium persulfate and ammonium persulfate; di(2-ethylhexyl)peroxydicarbonate, di(4-t-butylcyclohexyl)peroxydicarbonate, di-sec-butyl ... Examples of the initiator include, but are not limited to, peroxide initiators such as dicarbonate, t-butyl peroxyneodecanoate, t-hexyl peroxypivalate, t-butyl peroxypivalate, dilauroyl peroxide, di-n-octanoyl peroxide, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, di(4-methylbenzoyl)peroxide, dibenzoyl peroxide, t-butyl peroxyisobutyrate, 1,1-di(t-hexylperoxy)cyclohexane, t-butyl hydroperoxide, and hydrogen peroxide; and redox initiators that combine a peroxide and a reducing agent, such as a combination of a persulfate and sodium hydrogen sulfite, or a combination of a peroxide and sodium ascorbate.
[0058] The polymerization initiators can be used alone or in combination, but the total amount used is preferably about 0.005 to 1 part by weight, and more preferably about 0.02 to 0.5 part by weight, per 100 parts by weight of the monomer component.
[0059] Examples of the chain transfer agent include lauryl mercaptan, glycidyl mercaptan, mercaptoacetic acid, 2-mercaptoethanol, thioglycolic acid, 2-ethylhexyl thioglycolate, 2,3-dimercapto-1-propanol, etc. The chain transfer agent may be used alone or in combination of two or more kinds, but the total amount used is about 0.1 part by weight or less per 100 parts by weight of the monomer component.
[0060] Examples of emulsifiers used in emulsion polymerization include anionic emulsifiers such as sodium lauryl sulfate, ammonium lauryl sulfate, sodium dodecylbenzenesulfonate, ammonium polyoxyethylene alkyl ether sulfate, and sodium polyoxyethylene alkyl phenyl ether sulfate; and nonionic emulsifiers such as polyoxyethylene alkyl ether, polyoxyethylene alkyl phenyl ether, polyoxyethylene fatty acid ester, and polyoxyethylene-polyoxypropylene block polymer. The emulsifiers can be used alone or in combination.
[0061] Examples of the reactive emulsifier include emulsifiers having radical polymerizable functional groups such as propenyl and allyl ether groups. Specific examples of this emulsifier include Aqualon HS-10, HS-20, KH-10, BC-05, BC-10, and BC-20 (all manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), and Adeka Reasoap SE10N (manufactured by ADEKA Corporation). Reactive emulsifiers are preferred because they are incorporated into the polymer chain after polymerization and improve water resistance. The amount of emulsifier used is preferably 0.3 to 5 parts by weight per 100 parts by weight of the total amount of the monomer components, and more preferably 0.5 to 1 part by weight in terms of polymerization stability and mechanical stability.
[0062] In radiation polymerization, the monomer components are polymerized by irradiating them with radiation such as electron beams or UV rays to produce the (meth)acrylic polymer (A). When radiation polymerization is performed with electron beams, it is not particularly necessary to include a photopolymerization initiator in the monomer components. When radiation polymerization is performed with UV rays, the monomer components may contain a photopolymerization initiator due to the advantage that the polymerization time can be shortened. The photopolymerization initiators can be used alone or in combination.
[0063] The photopolymerization initiator is not particularly limited as long as it initiates photopolymerization, and a commonly used photopolymerization initiator can be used. As the photopolymerization initiator, for example, benzoin ether type, acetophenone type, α-ketol type, photoactive oxime type, benzoin type, benzyl type, benzophenone type, ketal type, thioxanthone type, etc. can be used. The amount of the photopolymerization initiator used is 0.05 to 1.5 parts by weight, preferably 0.1 to 1 part by weight, based on 100 parts by weight of the monomer component. The photopolymerization initiator can be used alone or in combination.
[0064] [Isocyanate-based crosslinking agent] As the isocyanate-based crosslinking agent, a compound having at least two isocyanate groups (isocyanate compound) can be used. The number of isocyanate groups contained in the isocyanate compound is preferably 3 or more. The upper limit of the number of isocyanate groups is not particularly limited, and is, for example, 5. Examples of the isocyanate compound include an aromatic isocyanate compound, an alicyclic isocyanate compound, and an aliphatic isocyanate compound. It is preferable that the isocyanate-based crosslinking agent can self-polymerize by reacting with water.
[0065] Examples of aromatic isocyanate compounds include phenylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 2,2'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-toluidine diisocyanate, 4,4'-diphenylether diisocyanate, 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, and xylylene diisocyanate.
[0066] Examples of alicyclic isocyanate compounds include 1,3-cyclopentene diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated tolylene diisocyanate, and hydrogenated tetramethylxylylene diisocyanate.
[0067] Examples of the aliphatic isocyanate compound include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.
[0068] Examples of the isocyanate-based crosslinking agent include polymers (dimers, trimers, pentamers, etc.) of the above-mentioned isocyanate compounds, adducts obtained by adding them to polyhydric alcohols such as trimethylolpropane, urea-modified products, biuret-modified products, allophanate-modified products, isocyanurate-modified products, carbodiimide-modified products, and urethane prepolymers obtained by adding them to polyether polyols, polyester polyols, acrylic polyols, polybutadiene polyols, polyisoprene polyols, and the like.
[0069] The isocyanate-based crosslinking agent is preferably an aromatic isocyanate compound and its derivatives, more preferably tolylene diisocyanate and its derivatives, in other words, a tolylene diisocyanate-based (TDI-based) crosslinking agent. From the viewpoint of reactivity, the TDI-based crosslinking agent is more suitable for the pressure-sensitive adhesive composition of the present embodiment than xylylene diisocyanate and its derivatives, in other words, a xylylene diisocyanate-based (XDI-based) crosslinking agent. The isocyanate-based crosslinking agent may contain an adduct of a polyhydric alcohol and tolylene diisocyanate as a TDI-based crosslinking agent. A specific example of this adduct is a trimethylolpropane / tolylene diisocyanate trimer adduct.
[0070] Commercially available isocyanate crosslinking agents include, for example, products manufactured by Tosoh Corporation under the trade names "Millionate MT", "Millionate MTL", "Millionate MR-200", "Millionate MR-400", "Coronate L", "Coronate HL", and "Coronate HX", and products manufactured by Mitsui Chemicals under the trade names "Takenate D-101E", "Takenate D-110N", "Takenate D-120N", "Takenate D-140N", "Takenate D-160N", "Takenate D-165N", "Takenate D-170HN", "Takenate D-178N", "Takenate 500", and "Takenate 600", with Takenate D-101E being preferred.
[0071] The isocyanate-based crosslinking agent may be used alone or in combination of two or more of the above. The amount of the isocyanate-based crosslinking agent is 2 parts by weight or more, preferably 3 parts by weight or more, more preferably 5 parts by weight or more, even more preferably 8 parts by weight or more, particularly preferably 10 parts by weight or more, and may be 11 parts by weight or more, relative to 100 parts by weight of the (meth)acrylic polymer (A). The amount of the isocyanate-based crosslinking agent may be, for example, 20 parts by weight or less, 15 parts by weight or less, 14 parts by weight or less, 13 parts by weight or less, or even 12 parts by weight or less, relative to 100 parts by weight of the (meth)acrylic polymer (A).
[0072] In the adhesive composition, when the amount of the isocyanate-based crosslinking agent per 100 parts by weight of the (meth)acrylic polymer (A) is as high as about 2 parts by weight or more, when the adhesive sheet is produced, the isocyanate-based crosslinking agents may react with each other to form a polymer (B) containing a structural unit derived from the isocyanate-based crosslinking agent as a main component. The polymer (B) is suitable for suppressing the dimensional change of the adhesive sheet by imparting sufficient cohesive force to the adhesive sheet. That is, the polymer (B) is suitable for suppressing display unevenness and light leakage in an image display device. Furthermore, the combination of the (meth)acrylic polymer (A) and the polymer (B) is suitable for improving the durability of the adhesive sheet under a high temperature and high humidity environment. In addition, in the adhesive composition of the present embodiment, by adjusting the amount of the isocyanate-based crosslinking agent per 100 parts by weight of the (meth)acrylic polymer (A) to, for example, 20 parts by weight or less (preferably 13 parts by weight or less), the elastic modulus of the adhesive sheet tends to be suppressed from becoming excessively high. The pressure-sensitive adhesive sheet formed from this pressure-sensitive adhesive composition can prevent stress from concentrating near the pressure-sensitive adhesive sheet during rework, thereby preventing breakage of components in the optical laminate.
[0073] [Polyhydroxyalkylamine compounds] As the polyhydroxyl alkylamine compound, an amine compound (C) having at least two hydroxyl groups can be used. The number of hydroxyl groups in the amine compound (C) may be 3 or more. The upper limit of the number of hydroxyl groups is not particularly limited, and is, for example, 5.
[0074] The number of nitrogen atoms (specifically, amino groups) contained in the amine compound (C) may be 1 or more, or may be 2 or more. The upper limit of the number of nitrogen atoms is not particularly limited and is, for example, 5.
[0075] Examples of the amine compound (C) having one nitrogen atom include dialcoholamines such as diethanolamine, dipropanolamine, diisopropanolamine, N-methyldiethanolamine, N-methyldiisopropanolamine, N-ethyldiethanolamine, N-ethyldiisopropanolamine, N-butyldiethanolamine, and N-butyldiisopropanolamine; and trialcoholamines such as triethanolamine, tripropanolamine, and triisopropanolamine.
[0076] The amine compound (C) having two nitrogen atoms includes a compound represented by the following formula (1). [ka]
[0077] In formula (1), R 1 , R 2 , R 3 and R 4 are each independently a hydrogen atom or a group represented by the general formula -(R 5 O) m (R 6 O) n In the above general formula, R 5 and R 6 are each independently an alkylene group. 5 The alkylene group of R 6 m and n are each independently an integer of 0 or more, provided that at least one of m and n is an integer of 1 or more. 1 , R 2 , R 3 and R 4 At least two of the general formula -(R 5 O) m (R 6 O) n -H and R 1 , R 2 , R 3 and R 4 Each of the general formula -(R 5 O) m (R 6 O)n It may be -H. X represents a divalent hydrocarbon group, and p is an integer of 1 or more.
[0078] R 5 and R 6 In the formula, examples of the alkylene group include alkylene groups having about 2 to 6 carbon atoms (preferably alkylene groups having 2 to 4 carbon atoms, more preferably alkylene groups having 2 or 3 carbon atoms), such as ethylene group, propylene group, trimethylene group, tetramethylene group, ethylethylene group, pentamethylene group, and hexamethylene group. The alkylene group may have either a linear or branched chain form. As the alkylene group, an ethylene group or a propylene group can be suitably used. m and n are, for example, 0 to 20, and preferably 1 to 10. One of m and n may be 0, and the other may be an integer of 1 or more (particularly 1).
[0079] In X, the divalent hydrocarbon group may be either saturated or unsaturated. Examples of the divalent hydrocarbon group include an alkylene group, a cycloalkylene group, and an arylene group. The alkylene group may be either linear or branched. Examples of the alkylene group include an alkylene group having about 1 to 6 carbon atoms, such as a methylene group, an ethylene group, a propylene group, a trimethylene group, and a tetramethylene group (preferably an alkylene group having 1 to 4 carbon atoms, and more preferably an alkylene group having 2 or 3 carbon atoms). Examples of the cycloalkylene group include a cycloalkylene group having about 5 to 12 membered rings, such as a 1,2-cyclohexylene group, a 1,3-cyclohexylene group, and a 1,4-cyclohexylene group. Examples of the arylene group include a 1,2-phenylene group, a 1,3-phenylene group, and a 1,4-phenylene group.
[0080] In formula (1), p is not particularly limited as long as it is an integer of 1 or more. For example, it is an integer of 1 to 10, preferably an integer of 1 to 6, and more preferably an integer of 1 to 4.
[0081] Examples of the amine compound (C) represented by formula (1) include N,N,N',N'-tetrakis(2-hydroxyethyl)ethylenediamine, N,N,N',N'-tetrakis(2-hydroxypropyl)ethylenediamine, N,N,N',N'-tetrakis(2-hydroxyethyl)trimethylenediamine, N,N,N',N'-tetrakis(2-hydroxypropyl)trimethylenediamine, etc. Other examples of the amine compound (C) represented by formula (1) include polyoxyalkylene condensates of alkylenediamines such as polyoxyethylene condensates of ethylenediamine, polyoxypropylene condensates of ethylenediamine, and polyoxyethylene-polyoxypropylene condensates of ethylenediamine. As the amine compound (C) represented by formula (1), for example, commercially available products such as those sold under the trade names "EDP-300", "EDP-450", "EDP-1100", and "Pluronic" (all manufactured by ADEKA Corporation) can be used.
[0082] The polyhydroxylalkylamine-based compounds may be used alone or in combination of two or more of the above-mentioned compounds.
[0083] The molecular weight of the polyhydroxyl alkylamine compound is, for example, 1500 or less, and may be 1000 or less, 800 or less, 500 or less, 400 or less, or even 300 or less. The smaller the molecular weight of the polyhydroxyl alkylamine compound, the easier it is to improve the reworkability of the pressure-sensitive adhesive sheet with a smaller amount of compounding. The lower limit of the molecular weight of the polyhydroxyl alkylamine compound is not particularly limited, and may be 100 or more, 200 or more, or in some cases 400 or more, or 1000 or more. When the molecular weight of the polyhydroxyl alkylamine compound is large, the pot life of the pressure-sensitive adhesive composition tends to be improved.
[0084] The amount of the polyhydroxylalkylamine compound is, for example, 0.01 to 5 parts by weight, and may be 0.1 parts by weight or more, based on 100 parts by weight of the (meth)acrylic polymer (A). This amount may be 3.5 parts by weight or less, 3 parts by weight or less, 2 parts by weight or less, 1.5 parts by weight or less, 1 part by weight or less, or even 0.5 parts by weight or less. When the amount of the polyhydroxylalkylamine compound is small, the pot life of the pressure-sensitive adhesive composition tends to be improved.
[0085] [Polyether compounds] The polyether compound is a compound having a polyether skeleton. When a pressure-sensitive adhesive sheet formed from the pressure-sensitive adhesive composition is attached to an adherend such as alkali-free glass, the polyether compound tends to segregate on the surface of the adherend, thereby reducing the adhesive strength (for example, adhesive strength P0 described below) between the pressure-sensitive adhesive sheet and the adherend. According to the study by the present inventors, in the pressure-sensitive adhesive sheet formed from the pressure-sensitive adhesive composition of the present embodiment, the polyhydroxyalkylamine compound tends to promote the segregation of the polyether compound. By promoting the segregation of the polyether compound, the adhesive strength between the pressure-sensitive adhesive sheet and the adherend is sufficiently reduced, and the reworkability of the pressure-sensitive adhesive sheet can be improved.
[0086] The polyether compound may contain a silicon atom and may further contain a hydroxyl group and / or a hydrolyzable group bonded to the silicon atom. The polyether compound has a group represented by the general formula -SiR a M 3-a In the above general formula, R is, independently of one another, a monovalent organic group having 1 to 20 carbon atoms which may have a substituent. M is, independently of one another, a hydroxyl group or a hydrolyzable group. a is an integer of 0 to 3, and may be an integer of 0 to 2 or an integer of 1 to 3.
[0087] For example, the polyether compound has at least one reactive silyl group per molecule at its end. When the polyether compound is linear, the polyether compound may have one or two reactive silyl groups at its end, and preferably has two reactive silyl groups. When the polyether compound is branched, the polyether compound has at least one reactive silyl group at the main chain end or the side chain end. The number of reactive silyl groups can be appropriately adjusted according to the number of ends of the polyether compound, and is preferably 2 or more, and may be 3 or more.
[0088] The polyether compound preferably has a reactive silyl group at least in part of its molecular terminals, and at least one, preferably 1.1 to 5, and more preferably 1.1 to 3 reactive silyl groups in the molecule.
[0089] In the above general formula, R is preferably a linear or branched alkyl group having 1 to 8 carbon atoms, a fluoroalkyl group having 1 to 8 carbon atoms, or a phenyl group, more preferably an alkyl group having 1 to 6 carbon atoms, and particularly preferably a methyl group. When a polyether compound contains multiple R, the multiple R may be the same as or different from each other.
[0090] In the above general formula, M, the hydrolyzable group is bonded to a silicon atom, and can form a siloxane bond by hydrolysis and / or condensation. Examples of the hydrolyzable group include halogen atoms, alkoxy groups, acyloxy groups, alkenyloxy groups, carbamoyl groups, amino groups, aminooxy groups, and ketoximate groups. When the hydrolyzable group has carbon atoms, the number of carbon atoms is preferably 6 or less, and more preferably 4 or less. In particular, an alkoxy group or an alkenyloxy group having 4 or less carbon atoms is preferred, and a methoxy group or an ethoxy group is particularly preferred. When multiple Ms are present in a polyether-based compound, the multiple Ms may be the same or different from each other.
[0091] The reactive silyl group is preferably an alkoxysilyl group represented by the following formula (2) or an alkoxysilyl group represented by the following formula (3). [ka]
[0092] In formula (2) and formula (3), R 7 , R 8 and R 9 are each independently a monovalent hydrocarbon group having 1 to 6 carbon atoms, examples of which include a linear or branched alkyl group having 1 to 6 carbon atoms, a linear or branched alkenyl group having 2 to 6 carbon atoms, a cycloalkyl group having 5 to 6 carbon atoms, and a phenyl group. 7 , -OR 8 -OR 9 Specific examples of the aryl group include a methoxy group, an ethoxy group, a propoxy group, a propenyloxy group, and a phenoxy group. Of these, a methoxy group and an ethoxy group are preferred, and a methoxy group is particularly preferred.
[0093] The polyether skeleton of the polyether compound preferably has a repeating unit of a linear or branched oxyalkylene group having 1 to 10 carbon atoms. The carbon number of the oxyalkylene group is preferably 2 to 6, and more preferably 3. In the polyether skeleton, the repeating unit of the oxyalkylene group may be one type or two or more types. When the polyether skeleton contains two or more types of repeating units, the repeating units may be arranged in a block shape or randomly. Specific examples of the oxyalkylene group include an oxyethylene group, an oxypropylene group, and an oxybutylene group. The oxyalkylene group is preferably an oxypropylene group (particularly, -CH2CH(CH3)O-) from the viewpoints of ease of production of the material and stability of the material.
[0094] The polyether compound preferably has a main chain substantially composed of a polyether skeleton, except for the reactive silyl group. However, the main chain of the polyether compound may contain a small amount of other chemical structures. Examples of the other chemical structures include a chemical structure derived from an initiator for forming a repeating unit of an oxyalkylene group, and a linking group between the polyether skeleton and the reactive silyl group. The content of the repeating unit of an oxyalkylene group in the polyether compound is preferably 50% by weight or more, more preferably 80% by weight or more.
[0095] The polyether compound may be a compound represented by the following formula (4). R a M 3-a Si-XY-(AO) n -Z (4)
[0096] In formula (4), R are each independently a monovalent organic group having 1 to 20 carbon atoms which may have a substituent. M are each independently a hydroxyl group or a hydrolyzable group. a is an integer of 0 to 3, and may be an integer of 0 to 2 or an integer of 1 to 3. AO is a linear or branched oxyalkylene group having 1 to 10 carbon atoms. n represents the average molar number of oxyalkylene groups added and is 1 to 1700. X is a linear or branched alkylene group having 1 to 20 carbon atoms. Y is an ether bond, an ester bond, a urethane bond, or a carbonate bond. Z is a hydrogen atom, a monovalent hydrocarbon group having 1 to 10 carbon atoms, a group represented by the following formula (5), or a group represented by the following formula (6). -Y1-X-SiR a M 3-a (5) -Q{-(OA) n -YX-SiR a M 3-a} m (6)
[0097] In formula (5), R, M, X, and a are the same as those in formula (4). Y1 is a single bond, a -CO- bond, a -CONH- bond, or a -COO- bond. In formula (6), R, M, X, Y, and n are the same as those in formula (4). OA is the same as AO in formula (4). Q is a divalent or higher hydrocarbon group having 1 to 10 carbon atoms. m is a value obtained by subtracting 1 from the valence of the hydrocarbon group of Q.
[0098] X in the formula (4) is a linear or branched alkylene group having 1 to 20 carbon atoms. The alkylene group preferably has 2 to 10 carbon atoms, and more preferably has 3 carbon atoms.
[0099] Y in formula (4) is a bond formed by reaction with a hydroxyl group of an oxyalkylene group at the end of the polyether skeleton, and is preferably an ether bond or a urethane bond, and more preferably a urethane bond.
[0100] Z is derived from, for example, an initiator (hydroxy compound) used in synthesizing an oxyalkylene polymer used in preparing a polyether compound represented by formula (4). When the polyether compound represented by formula (4) has one reactive silyl group at its end, Z may be a hydrogen atom or a monovalent hydrocarbon group having 1 to 10 carbon atoms. When Z is a hydrogen atom, this corresponds to the use of a hydroxy compound having the same structure as the structural unit contained in the oxyalkylene polymer. When Z is a monovalent hydrocarbon group having 1 to 10 carbon atoms, this corresponds to the use of a hydroxy compound having one hydroxyl group.
[0101] On the other hand, when the polyether compound represented by formula (4) has multiple reactive silyl groups at its terminal, Z may be a group represented by formula (5) or a group represented by formula (6). When Z is represented by formula (5), it corresponds to the case where a hydroxy compound having a structure similar to that of the structural unit contained in the oxyalkylene polymer is used. When Z is represented by formula (6), it corresponds to the case where a hydroxy compound having two hydroxyl groups and different from the structural unit contained in the oxyalkylene polymer is used. It should be noted that Y1 in formula (5) is a bond formed by reacting with the hydroxyl group of the oxyalkylene group at the terminal of the polyether skeleton, similar to Y in formula (4).
[0102] From the viewpoint of reworkability, the polyether compound is preferably represented by the following formula (7), formula (8) or formula (9). Z 0 -A 2 -O-(A 1 O) n -Z 1 (7) Z 0 -A 2 -NHCOO-(A 1 O) n -Z 2 (8) Z 3 -O-(A 1 O) n -CH{-CH2-(A 1 O) n -Z 3}2(9)
[0103] In formulas (7) to (9), Z 0 A is an alkoxysilyl group represented by formula (2) or formula (3). 1 O is an oxyalkylene group having 2 to 6 carbon atoms, and is preferably an oxypropylene group. 1 The oxyalkylene group of O may be linear or branched. 1 The average number of moles of O added is 1 to 1700. A in formula (7) and formula (8) 2 A is an alkylene group having 2 to 6 carbon atoms, and is preferably a propylene group.2 The alkylene group of formula (7) may be linear or branched. 1 is a hydrogen atom or -A 2 -Z 0 In equation (8), Z 2 is a hydrogen atom or -CONH-A 2 -Z 0 In equation (9), Z 3 is a hydrogen atom or -A 2 -Z 0 and there is at least one Z 3 Ga-A 2 -Z 0 It is.
[0104] As the compound represented by formula (8), for example, a compound represented by the following formula (10) is preferable. [ka]
[0105] In formula (10), R 7 , R 8 and R 9 are each independently a monovalent hydrocarbon group having 1 to 6 carbon atoms. n represents the average number of moles of oxypropylene groups added and is 1 to 1,700. 21 is a hydrogen atom or a trialkoxysilyl group represented by the following formula (11). [ka]
[0106] In formula (11), R 7 , R 8 and R 9 is the same as equation (10).
[0107] The number average molecular weight of the polyether-based compound is preferably 300 to 100,000 from the viewpoint of reworkability. The number average molecular weight is preferably 500 or more, 1,000 or more, 2,000 or more, 3,000 or more, 4,000 or more, or even 5,000 or more, and is preferably 50,000 or less, 40,000 or less, 30,000 or less, 20,000 or less, or even 10,000 or less. n (average number of moles of oxyalkylene groups added in the polyether skeleton) in the above formulas (4) and (7) to (10) is appropriately adjusted, for example, so that the number average molecular weight of the polyether-based compound is in the above range. When the number average molecular weight of the polyether-based compound is 1,000 or more, the above n is usually 10 to 1,700.
[0108] The Mw (weight average molecular weight) / Mn (number average molecular weight) of the polyether compound is preferably 3.0 or less, more preferably 1.6 or less, and particularly preferably 1.5 or less. In order to obtain a polyether compound having a small Mw / Mn, it is preferable to use an oxyalkylene polymer obtained by polymerizing a cyclic ether in the presence of an initiator using the composite metal cyanide complex described below as a catalyst, and a method of modifying the terminal of the oxyalkylene polymer to introduce a reactive silyl group is particularly preferable.
[0109] The polyether compounds represented by formulas (4), (7) to (10) can be produced, for example, by using an oxyalkylene polymer having a functional group at the molecular end as a raw material and bonding a reactive silyl group to the molecular end via an organic group such as an alkylene group. The oxyalkylene polymer used as a raw material is preferably a polymer having a hydroxyl group terminal obtained by ring-opening polymerization of a cyclic ether in the presence of a catalyst and an initiator.
[0110] As the initiator, a compound having one or more active hydrogen atoms per molecule, for example, a hydroxy compound having one or more hydroxyl groups per molecule, can be used. Examples of the initiator include ethylene glycol, propylene glycol, dipropylene glycol, butanediol, hexamethylene glycol, hydrogenated bisphenol A, neopentyl glycol, polybutadiene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, allyl alcohol, methallyl alcohol, glycerin, trimethylolmethane, trimethylolpropane, pentaerythritol, and hydroxy compounds such as alkylene oxide adducts thereof. The initiator may be one or more kinds.
[0111] When the cyclic ether is subjected to ring-opening polymerization in the presence of an initiator, a polymerization catalyst can be used. Examples of the polymerization catalyst include alkali metal compounds such as potassium hydroxide, potassium methoxide, and cesium compounds such as cesium hydroxide; composite metal cyanide complexes; metal porphyrin complexes; and compounds having a P=N bond.
[0112] The polyether skeleton (polyoxyalkylene chain) in the polyether compounds represented by formulae (4), (7) to (10) is preferably composed of repeating units of an oxyalkylene group formed by ring-opening polymerization of an alkylene oxide having 2 to 6 carbon atoms, more preferably composed of repeating units of an oxyalkylene group formed by ring-opening polymerization of at least one alkylene oxide selected from the group consisting of ethylene oxide, propylene oxide and butylene oxide, and particularly preferably composed of repeating units of an oxyalkylene group formed by ring-opening polymerization of propylene oxide. When the polyoxyalkylene chain is composed of repeating units of two or more kinds of oxyalkylene groups, the repeating units of the two or more kinds of oxyalkylene groups may be arranged in a block form or a random form.
[0113] The polyether compound represented by the above formula (8) can be obtained, for example, by subjecting a polymer having a polyoxyalkylene chain and a hydroxyl group to a urethane reaction using a compound having a reactive silyl group and an isocyanate group. The polyether compound can also be obtained by adding hydrosilane or mercaptosilane to the unsaturated group of an oxyalkylene polymer having an unsaturated group, for example, an allyl-terminated polyoxypropylene monol obtained by polymerizing an alkylene oxide using allyl alcohol as an initiator, to introduce a reactive silyl group into the molecular end.
[0114] The method for introducing a reactive silyl group into the end group of a hydroxyl-terminated oxyalkylene polymer obtained by ring-opening polymerization of a cyclic ether in the presence of an initiator is not particularly limited, and the following methods (a) to (c) in which a reactive silyl group is further linked to the end group via an organic group are preferred.
[0115] (a) A method in which an unsaturated group is introduced at the end of an oxyalkylene polymer having a hydroxyl group, and then a reactive silyl group is bonded to this unsaturated group. As this method, the following two methods (a-1) and (a-2) can be further exemplified: (a-1) A method using a so-called hydrosilylation reaction in which a hydrosilyl compound is reacted with the unsaturated group in the presence of a catalyst such as a platinum compound. (a-2) A method of reacting an unsaturated group with a mercaptosilane compound.
[0116] Examples of the mercaptosilane compound (a-2) include 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropyltriisopropenyloxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyldimethylmonomethoxysilane, and 3-mercaptopropylmethyldiethoxysilane.
[0117] When reacting an unsaturated group with a mercapto group, a compound such as a radical generator used as a radical polymerization initiator may be used, or the reaction may be carried out by radiation or heat without using a radical polymerization initiator if desired. Examples of the radical polymerization initiator include peroxide-based, azo-based and redox-based polymerization initiators, as well as metal compound catalysts, and specific examples include 2,2'-azobisisobutyronitrile, 2,2'-azobis-2-methylbutyronitrile, benzoyl peroxide, tert-alkyl peroxy ester, acetyl peroxide and diisopropyl peroxycarbonate. The reaction conditions when reacting an unsaturated group with a mercapto group using a radical polymerization initiator vary depending on the decomposition temperature (half-life temperature) of the polymerization initiator, but it is preferable to carry out the reaction for several hours to several tens of hours at a reaction temperature of 20 to 200°C, preferably 50 to 150°C.
[0118] The method of introducing an unsaturated group into the terminal of an oxyalkylene polymer includes a method of reacting an oxyalkylene polymer with a functional group capable of linking the terminal hydroxyl group of the oxyalkylene polymer with an ether bond, an ester bond, a urethane bond, a carbonate bond, or the like, and a reactant having an unsaturated group. A method of introducing an unsaturated group into at least a part of the terminal of an oxyalkylene polymer by copolymerizing an unsaturated group-containing epoxy compound such as allyl glycidyl ether when polymerizing a cyclic ether in the presence of an initiator can also be used.
[0119] The hydrosilylation reaction is preferably carried out at a temperature of 60 to 120° C. In general, the hydrosilylation reaction proceeds sufficiently within a reaction time of several hours.
[0120] (b) A method of reacting an oxyalkylene polymer having a hydroxyl group at its terminal with an isocyanate silane compound having a reactive silyl group. Examples of the isocyanate silane compound include isocyanate silane compounds such as 1-isocyanate methyl trimethoxysilane, 1-isocyanate methyl triethoxysilane, 1-isocyanate propyl trimethoxysilane, 1-isocyanate propyl triethoxysilane, 3-isocyanate propyl trimethoxysilane, 3-isocyanate propyl triethoxysilane, 1-isocyanate methyl methyl dimethoxysilane, 1-isocyanate methyl dimethyl monomethoxysilane, 1-isocyanate methyl methyl diethoxysilane, 1-isocyanate propyl methyl dimethoxysilane, 1-isocyanate propyl dimethyl monomethoxysilane, 1-isocyanate propyl methyl diethoxysilane, 3-isocyanate propyl methyl dimethoxysilane, 3-isocyanate propyl dimethyl monomethoxysilane, and 3-isocyanate propyl methyl diethoxysilane. Of these, 3-isocyanatepropyltrimethoxysilane and 1-isocyanatemethyldimethoxysilane are more preferred, and 3-isocyanatepropyltrimethoxysilane is particularly preferred.
[0121] The reaction between the oxyalkylene polymer and the isocyanate silane compound is preferably carried out so that the molar ratio of the isocyanate group (NCO) of the isocyanate silane compound to the hydroxyl group (OH) of the oxyalkylene polymer is NCO / OH=0.80-1.05. This method can significantly shorten the process time because of the small number of manufacturing steps, and does not require complicated operations such as purification because there are few impurities produced as by-products during the manufacturing process. A more preferable molar ratio of NCO group to OH group is NCO / OH=0.85-1.00. When the ratio of NCO is low, the remaining OH group reacts with the reactive silyl group, etc., and the storage stability may decrease. In this case, it is preferable to adjust the silylation rate to a predetermined level by newly reacting with the isocyanate silane compound or monoisocyanate compound and consuming the excess OH group.
[0122] When the hydroxyl group of the oxyalkylene polymer is reacted with the above-mentioned isocyanate silane compound, a known urethanization catalyst may be used. The reaction temperature and the reaction time required for the reaction to be completed vary depending on the presence or absence of the urethanization catalyst and the amount of the catalyst used, but the reaction between the oxyalkylene polymer and the isocyanate silane compound is preferably carried out at a temperature of, for example, 20 to 200°C, preferably 50 to 150°C, for several hours.
[0123] (c) A method in which an oxyalkylene polymer having a hydroxyl group at the molecular terminal is reacted with a polyisocyanate compound under conditions of an excess of isocyanate groups to produce an oxyalkylene polymer having an isocyanate group at at least a portion of the terminals, and then the isocyanate group is reacted with a silicon compound having a functional group. The functional group of the silicon compound is at least one active hydrogen-containing group selected from the group consisting of hydroxyl, carboxyl, mercapto, primary amino and secondary amino groups. Examples of silicon compounds include aminosilane-based compounds such as N-phenyl-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-phenyl-3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldimethoxysilane and 3-aminopropylmethyldiethoxysilane; and mercaptosilane-based compounds such as 3-mercaptopropyltrimethoxysilane and 3-mercaptopropylmethyldimethoxysilane. When reacting the oxyalkylene polymer with the silicon compound, a known urethanization catalyst may be used. The reaction temperature and the reaction time required to complete the reaction vary depending on the presence or absence of the urethanization catalyst and the amount of the catalyst used, but the reaction is preferably carried out at a temperature of, for example, 20 to 200°C, preferably 50 to 150°C for several hours.
[0124] Specific examples of polyether compounds include MS Polymer S203, S303, S810, SILYL EST250, EST280, SAT10, SAT200, SAT220, SAT350, SAT400 manufactured by Kaneka Corporation, and EXCESTAR S2410, S2420, S3430 manufactured by AGC.
[0125] The amount of the polyether compound is, for example, 0.1 to 5 parts by weight, and may be 0.3 parts by weight or more, or even 0.5 parts by weight or more, relative to 100 parts by weight of the (meth)acrylic polymer (A). This amount may be 4 parts by weight or less, 3 parts by weight or less, 2 parts by weight or less, or even 1 part by weight or less.
[0126] [Other ingredients] The pressure-sensitive adhesive composition may contain a crosslinking agent other than the isocyanate-based crosslinking agent. Examples of the other crosslinking agent include a peroxide-based crosslinking agent, an epoxy-based crosslinking agent, an imine-based crosslinking agent, and a polyfunctional metal chelate. The amount of the other crosslinking agent is preferably 2 parts by weight or less, more preferably 1 part by weight or less, based on 100 parts by weight of the (meth)acrylic polymer (A). From the viewpoint of durability of the pressure-sensitive adhesive sheet, the pressure-sensitive adhesive composition may be substantially free of other crosslinking agents, particularly epoxy-based crosslinking agents.
[0127] The pressure-sensitive adhesive composition may further contain a (meth)acrylic oligomer.
[0128] The (meth)acrylic oligomer may have the same composition as the above-mentioned (meth)acrylic polymer (A) except for the weight average molecular weight (Mw). The weight average molecular weight (Mw) of the (meth)acrylic oligomer may be, for example, 1000 or more, 2000 or more, 3000 or more, or even 4000 or more. The upper limit of the weight average molecular weight (Mw) of the (meth)acrylic oligomer may be, for example, 30000 or less, 15000 or less, 10000 or less, or even 7000 or less.
[0129] The (meth)acrylic oligomer has, for example, one or more structural units derived from each of the following monomers: methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, ) acrylate, alkyl (meth)acrylates such as nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, and dodecyl (meth)acrylate; esters of (meth)acrylic acid and alicyclic alcohols such as cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, and dicyclopentanyl (meth)acrylate; aromatic ring-containing (meth)acrylates such as phenyl (meth)acrylate and benzyl (meth)acrylate; and (meth)acrylates obtained from terpene compound derivative alcohols.
[0130] The (meth)acrylic oligomer preferably has a structural unit derived from a (meth)acrylic monomer having a relatively bulky structure. In this case, the adhesiveness of the pressure-sensitive adhesive sheet can be further improved. Examples of the acrylic monomer include alkyl (meth)acrylates having an alkyl group with a branched structure, such as isobutyl (meth)acrylate and t-butyl (meth)acrylate; esters of (meth)acrylic acid and alicyclic alcohol, such as cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, and dicyclopentanyl (meth)acrylate; and aromatic ring-containing (meth)acrylates, such as phenyl (meth)acrylate and benzyl (meth)acrylate. The monomer preferably has a cyclic structure, more preferably has two or more cyclic structures. Furthermore, when ultraviolet irradiation is performed during polymerization of the (meth)acrylic oligomer and / or formation of the pressure-sensitive adhesive sheet, since the progress of the polymerization and / or formation is less likely to be hindered, it is preferable that the above-mentioned monomer does not have an unsaturated bond. For example, an alkyl (meth)acrylate having an alkyl group with a branched structure, or an ester of (meth)acrylic acid and an alicyclic alcohol can be used.
[0131] Specific examples of the (meth)acrylic oligomer include a copolymer of butyl acrylate, methyl acrylate, and acrylic acid, a copolymer of cyclohexyl methacrylate and isobutyl methacrylate, a copolymer of cyclohexyl methacrylate and isobornyl methacrylate, a copolymer of cyclohexyl methacrylate and acryloylmorpholine, a copolymer of cyclohexyl methacrylate and diethylacrylamide, a copolymer of 1-adamantyl acrylate and methyl methacrylate, a copolymer of dicyclopentanyl methacrylate and isobornyl methacrylate, a copolymer of at least one selected from dicyclopentanyl methacrylate, cyclohexyl methacrylate, isobornyl methacrylate, isobornyl acrylate, and cyclopentanyl methacrylate and methyl methacrylate, a homopolymer of dicyclopentanyl acrylate, a homopolymer of 1-adamantyl methacrylate, and a homopolymer of 1-adamantyl acrylate.
[0132] For the polymerization of the (meth)acrylic oligomer, the above-mentioned polymerization method for the (meth)acrylic polymer (A) can be used.
[0133] When the pressure-sensitive adhesive composition contains a (meth)acrylic oligomer, the blending amount thereof may be, for example, 70 parts by weight or less, 50 parts by weight or less, or even 40 parts by weight or less, relative to 100 parts by weight of the (meth)acrylic polymer (A). The lower limit of the blending amount may be, for example, 1 part by weight or more, 2 parts by weight or more, or even 3 parts by weight or more, relative to 100 parts by weight of the (meth)acrylic polymer (A). The pressure-sensitive adhesive composition may not contain a (meth)acrylic oligomer.
[0134] The adhesive composition may further contain known additives. Examples of additives include rework improvers other than polyether compounds, silane coupling agents, solvents, colorants, powders such as pigments, dyes, surfactants, plasticizers, tackifiers, surface lubricants, leveling agents, softeners, antioxidants, antiaging agents, light stabilizers, UV absorbers, polymerization inhibitors, inorganic or organic fillers, metal powders, particles, foils, and the like. Furthermore, within a controllable range, a redox system containing a reducing agent may be used. From the viewpoint of improving the durability of the adhesive sheet, the adhesive composition preferably contains a silane coupling agent as an additive. These additives can be used in an amount of, for example, 10 parts by weight or less, preferably 5 parts by weight or less, more preferably 1 part by weight or less, relative to 100 parts by weight of the (meth)acrylic polymer (A).
[0135] Specific examples of the silane coupling agent include epoxy group-containing silane coupling agents such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; amino group-containing silane coupling agents such as 3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylidene)propylamine, and N-phenyl-γ-aminopropyltrimethoxysilane; (meth)acrylic group-containing silane coupling agents such as 3-acryloxypropyltrimethoxysilane and 3-methacryloxypropyltriethoxysilane; and isocyanate group-containing silane coupling agents such as 3-isocyanatepropyltriethoxysilane.
[0136] When the pressure-sensitive adhesive composition contains a silane coupling agent, the amount of the silane coupling agent may be, for example, 5 parts by weight or less, 3 parts by weight or less, 1 part by weight or less, 0.5 parts by weight or less, 0.4 parts by weight or less, 0.2 parts by weight or less, 0.1 parts by weight or less, or even 0.05 parts by weight or less, based on 100 parts by weight of the (meth)acrylic polymer (A). The lower limit of the amount of the silane coupling agent is not particularly limited, and is, for example, 0.02 parts by weight or more. The pressure-sensitive adhesive composition may not contain a silane coupling agent.
[0137] The type of the adhesive composition is, for example, an emulsion type, a solvent type (solution type), an active energy ray curing type (photocuring type), or a hot melt type (hot melt type). From the viewpoint of forming an adhesive sheet having excellent durability, the adhesive composition may be a solvent type. The solvent type adhesive composition may not substantially contain a photocuring agent such as an ultraviolet curing agent.
[0138] (Embodiment of the adhesive sheet) An example of the adhesive sheet of this embodiment is shown in FIG. 1. The adhesive sheet 1 of this embodiment is formed from the above-mentioned adhesive composition. The adhesive sheet 1 includes, for example, a crosslinked product of a (meth)acrylic polymer (A) and a polymer (B) containing a structural unit derived from an isocyanate-based crosslinking agent as a main component. In the polymer (B), the content of the structural unit derived from an isocyanate-based crosslinking agent is, for example, 70% by weight or more, preferably 90% by weight or more. The polymer (B) is, for example, substantially composed of only a structural unit derived from an isocyanate-based crosslinking agent. In the adhesive sheet 1, the crosslinked product of the (meth)acrylic polymer (A) and the polymer (B) may form an interpenetrating network (IPN) structure. This IPN structure is suitable for increasing the elastic modulus of the adhesive sheet 1 while improving its durability.
[0139] The thickness of the pressure-sensitive adhesive sheet 1 is not particularly limited and is, for example, about 1 to 100 μm, preferably 2 to 50 μm, more preferably 2 to 40 μm, and even more preferably 5 to 35 μm.
[0140] The method for producing the pressure-sensitive adhesive sheet 1 includes, for example, applying the above-mentioned pressure-sensitive adhesive composition to a substrate to form a coating film, and drying the resulting coating film.
[0141] As the substrate, for example, a release film can be used. The pressure-sensitive adhesive sheet 1 formed on the release film can be transferred to, for example, an optical film. The substrate may be an optical film. In this case, an optical laminate can be obtained by forming the pressure-sensitive adhesive sheet 1.
[0142] The release film can be used as a release liner after the pressure-sensitive adhesive sheet 1 is transferred to the optical film until the pressure-sensitive adhesive sheet 1 is put to practical use, allowing for simplification in terms of the process.
[0143] Examples of materials constituting the release film include suitable thin materials such as plastic films, porous materials such as paper, cloth, and nonwoven fabrics, nets, foam sheets, metal foils, and laminates of these, but plastic films are preferably used because of their excellent surface smoothness.
[0144] The plastic film is not particularly limited, and examples thereof include a polyethylene film, a polypropylene film, a polybutene film, a polybutadiene film, a polymethylpentene film, a polyvinyl chloride film, a vinyl chloride copolymer film, a polyethylene terephthalate film, a polybutylene terephthalate film, a polyurethane film, and an ethylene-vinyl acetate copolymer film.
[0145] The thickness of the release film is usually 5 to 200 μm, preferably about 5 to 100 μm. The release film is subjected to a release treatment such as a silicone-based, fluorine-based, or long-chain alkyl-based treatment. The release film may be subjected to a release and antifouling treatment using a fatty acid amide-based release agent or silica powder, or an antistatic treatment such as a coating type, kneading type, or deposition type.
[0146] A solution containing a pressure-sensitive adhesive composition (pressure-sensitive adhesive solution) may be applied to the substrate. The solid content of the pressure-sensitive adhesive solution is, for example, 5 to 50% by weight, and preferably 10 to 40% by weight. The pressure-sensitive adhesive solution can be prepared by appropriately adding the same solvent as the polymerization solvent or a different solvent to the pressure-sensitive adhesive composition depending on the polymerization form of the (meth)acrylic polymer (A).
[0147] Various methods are used to apply the pressure-sensitive adhesive composition to a substrate, including, for example, roll coating, kiss roll coating, gravure coating, reverse coating, roll brushing, spray coating, dip roll coating, bar coating, knife coating, air knife coating, curtain coating, lip coating, extrusion coating using a die coater, etc. The amount of the pressure-sensitive adhesive composition to be applied can be appropriately adjusted depending on the desired thickness of the pressure-sensitive adhesive sheet 1.
[0148] The coating film is dried to harden the coating film, forming the adhesive sheet 1. The drying temperature of the coating film is not particularly limited, and is, for example, 130° C. or less, preferably 125° C. or less, more preferably 120° C. or less, even more preferably 110° C. or less, and particularly preferably 100° C. or less. The drying temperature of the coating film may be 60° C. or more, or 80° C. or more. When the drying temperature is 60° C. or more, for example, the reaction of the isocyanate-based crosslinking agent proceeds smoothly, the cohesive force of the adhesive sheet 1 can be improved, and display unevenness of the image display device tends to be reduced. When the drying temperature is 130° C. or less, for example, the reaction rate of the isocyanate-based crosslinking agent can be appropriately adjusted, and the compatibility between the (meth)acrylic polymer (A) and the polymer (B) can be well maintained, and transparency tends to be ensured.
[0149] The drying time for the coating film can be appropriately adjusted depending on the components of the pressure-sensitive adhesive composition, and is preferably 30 to 300 seconds, more preferably 40 to 240 seconds, and particularly preferably 60 to 180 seconds.
[0150] [Characteristics of adhesive sheet] It is preferable that the pressure-sensitive adhesive sheet 1 has high transparency. When the thickness of the pressure-sensitive adhesive sheet 1 is 75 μm, the haze of the pressure-sensitive adhesive sheet 1 is, for example, 1% or less (or less than 1%), preferably 0.8% or less, and more preferably 0.6% or less.
[0151] The storage modulus G' of the pressure-sensitive adhesive sheet 1 at 25°C is not particularly limited, and may be, for example, 0.4 MPa or more, 0.5 MPa or more, 0.8 MPa or more, 1.0 MPa or more, or even 1.2 MPa or more. The upper limit of the storage modulus G' of the pressure-sensitive adhesive sheet 1 at 25°C is not particularly limited, and is, for example, 5.0 MPa. A high-modulus pressure-sensitive adhesive sheet 1 having a storage modulus G' within the above range is suitable for suppressing dimensional changes in an optical film.
[0152] The storage modulus G' of the adhesive sheet 1 at 25°C can be determined by the following method. First, a measurement sample made of the material constituting the adhesive sheet 1 is prepared. The shape of the measurement sample is disk-shaped. The measurement sample has a bottom diameter of 8 mm and a thickness of 2 mm. The measurement sample may be a disk-shaped punched out laminate in which a plurality of adhesive sheets 1 are laminated. Next, dynamic viscoelasticity measurement is performed on the measurement sample. For example, "ARES-G2" manufactured by TA Instruments can be used for the dynamic viscoelasticity measurement. The storage modulus G' of the adhesive sheet 1 at 25°C can be determined from the results of the dynamic viscoelasticity measurement. The conditions for the dynamic viscoelasticity measurement are as follows. Measurement conditions Frequency: 1Hz Deformation mode: Torsion Measurement temperature: -70℃~150℃ Heating rate: 5℃ / min
[0153] In the adhesive sheet 1, the gel fraction is not particularly limited, and is, for example, 60% to 99%. The gel fraction of the adhesive sheet 1 is preferably 80% or more, more preferably 90% or more, even more preferably 94% or more, and particularly preferably 95% or more. The gel fraction of the adhesive sheet 1 can be evaluated, for example, by the following method. First, a part of the adhesive sheet 1 is scraped off to obtain a small piece. Next, the obtained small piece is wrapped in a stretched porous film of polytetrafluoroethylene and tied with a kite string. This results in a test piece. Next, the total weight (weight A) of the small piece of the adhesive sheet 1, the stretched porous film, and the kite string is measured. The total weight of the stretched porous film and the kite string used is defined as weight B. Next, the test piece is immersed in a container filled with ethyl acetate and left to stand at 23°C for one week. After standing, the test piece is taken out of the container and dried in a dryer set at 130°C for two hours, and then the weight C of the test piece is measured. The gel fraction of the pressure-sensitive adhesive sheet 1 can be calculated from weight A, weight B, and weight C based on the following formula. Gel fraction (wt%)=(CB) / (AB)×100
[0154] (Embodiment of Optical Laminate) An example of the optical laminate of this embodiment is shown in Fig. 2. The optical laminate 10A in Fig. 2 includes an adhesive sheet 1 and an optical film 2. The adhesive sheet 1 and the optical film 2 are laminated to each other. The optical laminate 10A can be used as an optical film with an adhesive sheet.
[0155] Examples of the optical film 2 include a polarizing film, a retardation film, and a laminated film including a polarizing film and / or a retardation film. However, the optical film 2 is not limited to the above examples. The optical film 2 may include a glass film.
[0156] The polarizing film is, for example, a laminate including a polarizer and a protective film (transparent protective film). The transparent protective film is, for example, disposed in contact with the main surface (the surface having the widest area) of the layered polarizer. The polarizer may be disposed between two transparent protective films.
[0157] The polarizer is not particularly limited, and various polarizers can be used. Examples of the polarizer include a hydrophilic polymer film such as a polyvinyl alcohol film, a partially formalized polyvinyl alcohol film, or an ethylene-vinyl acetate copolymer partially saponified film, which is uniaxially stretched after adsorbing a dichroic substance such as iodine or a dichroic dye; a polyene-based oriented film such as a dehydrated polyvinyl alcohol or a dehydrochlorinated polyvinyl chloride; and the like. Among these, a polarizer made of a polyvinyl alcohol film and a dichroic substance such as iodine is preferred, and an iodine-based polarizer containing iodine and / or iodine ions is more preferred. The thickness of the polarizer is not particularly limited, but is generally about 5 to 80 μm.
[0158] A polarizer obtained by dyeing a polyvinyl alcohol-based film with iodine and stretching it uniaxially can be produced, for example, by dyeing the polyvinyl alcohol by immersing it in an aqueous solution of iodine and stretching it to 3 to 7 times its original length. If necessary, the polyvinyl alcohol can also be immersed in an aqueous solution of potassium iodide containing boric acid, zinc sulfate, zinc chloride, or the like. Furthermore, if necessary, the polyvinyl alcohol-based film may be immersed in water and washed before dyeing. Washing the polyvinyl alcohol-based film with water not only makes it possible to wash off dirt and antiblocking agents on the surface of the polyvinyl alcohol-based film, but also has the effect of suppressing the occurrence of uneven dyeing by swelling the polyvinyl alcohol-based film. The stretching of the polyvinyl alcohol-based film may be performed after dyeing with iodine, may be performed while dyeing, or may be performed before dyeing with iodine. The stretching may be performed in an aqueous solution of boric acid, potassium iodide, or the like, or in a water bath.
[0159] As the polarizer, a thin polarizer having a thickness of 10 μm or less can also be used. From the viewpoint of thinning, the thickness of the polarizer is preferably 1 to 7 μm. Such a thin polarizer is preferable in that it has less thickness unevenness, excellent visibility, and excellent durability due to less dimensional change, and further allows the polarizing film to be thinned.
[0160] Representative examples of the thin polarizer include the thin polarizers described in JP-A-51-069644, JP-A-2000-338329, WO-A-2010 / 100917, Japanese Patent No. 4751481, and JP-A-2012-073563. These thin polarizers can be obtained by a manufacturing method including a step of stretching a polyvinyl alcohol-based resin (hereinafter also referred to as PVA-based resin) layer and a resin substrate for stretching in a laminated state, and a step of dyeing. With this manufacturing method, since the PVA-based resin layer is supported by the resin substrate for stretching, even if the PVA-based resin layer is thin, defects such as breakage due to stretching can be suppressed.
[0161] Among the manufacturing methods including a step of stretching the laminate and a step of dyeing it, the manufacturing methods including a step of stretching in an aqueous boric acid solution described in WO 2010 / 100917, Japanese Patent No. 4751481, and JP 2012-073563 A are preferred because they enable stretching at a high ratio and improve polarization performance, and in particular, the manufacturing methods including a step of auxiliary air-stretching before stretching in an aqueous boric acid solution described in Japanese Patent No. 4751481 and JP 2012-073563 A are preferred.
[0162] As a material for forming the transparent protective film provided on one or both sides of the polarizer, for example, a thermoplastic resin excellent in transparency, mechanical strength, thermal stability, moisture blocking property, isotropy, etc. is used. Specific examples of such thermoplastic resins include cellulose resins such as triacetyl cellulose, polyester resins, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth)acrylic resins, cyclic polyolefin resins (norbornene-based resins), polyarylate resins, polystyrene resins, polyvinyl alcohol resins, and mixtures thereof. The material of the transparent protective film may be a thermosetting resin or an ultraviolet-curing resin such as a (meth)acrylic, urethane, acrylic urethane, epoxy, or silicone-based resin. When the polarizing film has two transparent protective films, the materials of the two transparent protective films may be the same or different from each other. For example, a transparent protective film made of a thermoplastic resin may be attached to one main surface of the polarizer via an adhesive, and a transparent protective film made of a thermosetting resin or an ultraviolet-curable resin may be attached to the other main surface of the polarizer. The transparent protective film may contain one or more types of optional additives. Examples of additives include ultraviolet absorbers, antioxidants, lubricants, plasticizers, release agents, coloring inhibitors, flame retardants, nucleating agents, antistatic agents, pigments, and colorants. The content of the thermoplastic resin in the transparent protective film is preferably 50 to 100% by weight, more preferably 50 to 99% by weight, even more preferably 60 to 98% by weight, and particularly preferably 70 to 97% by weight. When the content of the thermoplastic resin in the transparent protective film is 50% by weight or more, the inherent high transparency of the thermoplastic resin tends to be fully exhibited.
[0163] The thickness of the transparent protective film can be determined appropriately, but is generally about 10 to 200 μm in terms of strength, workability such as handleability, thinness, and the like.
[0164] The polarizer and the transparent protective film are usually adhered to each other via a water-based adhesive or the like. Examples of the water-based adhesive include an isocyanate-based adhesive, a polyvinyl alcohol-based adhesive, a gelatin-based adhesive, a vinyl-based latex, a water-based polyurethane, and a water-based polyester. Examples of adhesives other than the above-mentioned adhesives include an ultraviolet-curable adhesive and an electron beam-curable adhesive. The electron beam-curable polarizing film adhesive exhibits suitable adhesion to various transparent protective films. The adhesive may contain a metal compound filler.
[0165] In the case of a polarizing film, a retardation film or the like can be formed on the polarizer instead of the transparent protective film. Another transparent protective film or a retardation film or the like can be further provided on the transparent protective film.
[0166] The transparent protective film may have a hard coat layer on the surface opposite to the surface bonded to the polarizer, and may also be subjected to treatments for the purposes of anti-reflection, anti-sticking, diffusion, anti-glare, etc.
[0167] The polarizing film may be a circular polarizing film.
[0168] The retardation film may be one obtained by stretching a polymer film or one obtained by aligning and fixing a liquid crystal material. The retardation film has birefringence, for example, in the in-plane and / or thickness direction.
[0169] Examples of retardation films include anti-reflection retardation films (see JP 2012-133303 A,
[0221] ,
[0222] ,
[0228] ), viewing angle compensation retardation films (see JP 2012-133303 A,
[0225] ,
[0226] ), and tilted orientation retardation films for viewing angle compensation (see JP 2012-133303 A,
[0227] ).
[0170] As the retardation film, as long as it substantially has the above-mentioned functions, for example, the retardation value, arrangement angle, three-dimensional birefringence, whether it is a single layer or a multilayer, and the like are not particularly limited, and a known retardation film can be used.
[0171] The thickness of the retardation film is, for example, 20 μm or less, preferably 15 μm or less, more preferably 10 μm or less, further preferably 1 to 9 μm, and particularly preferably 3 to 8 μm.
[0172] Another example of the optical laminate of the present embodiment is shown in Fig. 3. The optical laminate 10B in Fig. 3 has a laminated structure in which an optical film 2, an adhesive sheet 1, and a release liner 3 are laminated in this order. By peeling off the release liner 3, the optical laminate 10B can be used as an optical film with an adhesive sheet.
[0173] Examples of materials constituting the release liner 3 include plastic films such as polyethylene, polypropylene, polyethylene terephthalate, and polyester film; porous materials such as paper, cloth, and nonwoven fabric; and appropriate thin materials such as nets, foam sheets, metal foils, and laminates of these. Plastic films are preferably used because of their excellent surface smoothness.
[0174] The plastic film is not particularly limited as long as it is a film capable of protecting the adhesive sheet 1, and examples include polyethylene film, polypropylene film, polybutene film, polybutadiene film, polymethylpentene film, polyvinyl chloride film, vinyl chloride copolymer film, polyethylene terephthalate film, polybutylene terephthalate film, polyurethane film, ethylene-vinyl acetate copolymer film, etc.
[0175] The thickness of the release liner 3 is usually 5 to 200 μm, and preferably about 5 to 100 μm. The release liner 3 may be subjected to a release and antifouling treatment using a silicone-based, fluorine-based, long-chain alkyl-based or fatty acid amide-based release agent, silica powder, or the like, as necessary, or an antistatic treatment such as a coating type, kneading type or deposition type. In particular, by appropriately performing a release treatment such as a silicone treatment, a long-chain alkyl treatment or a fluorine treatment on the surface of the release liner 3, the releasability from the pressure-sensitive adhesive sheet 1 can be further improved.
[0176] As described above, the release film used when producing the pressure sensitive adhesive sheet 1 may be used as the release liner 3.
[0177] Another example of the optical laminate of the present embodiment is shown in Fig. 4. The optical laminate 10C in Fig. 4 has a laminated structure in which a polarizing film 2A, an interlayer adhesive 4, a retardation film 2B, an adhesive sheet 1, and a release liner 3 are laminated in this order. After the release liner 3 is peeled off, the optical laminate 10C can be used by being attached to, for example, an image forming layer.
[0178] A known adhesive can be used as the interlayer adhesive 4. The adhesive sheet 1 may be used as the interlayer adhesive 4.
[0179] Another example of the optical laminate of this embodiment is shown in Fig. 5. The optical laminate 10D in Fig. 5 has a polarizing film 2A, a first retardation film 2B, and a second retardation film 2C as the optical film 2. In detail, the optical laminate 10D has a laminated structure in which the polarizing film 2A, the interlayer adhesive 4A, the first retardation film 2B, the interlayer adhesive 4B, the second retardation film 2C, the adhesive sheet 1, and the release liner 3 are laminated in this order. After the release liner 3 is peeled off, the optical laminate 10D can be used by being attached to, for example, an image forming layer.
[0180] Known adhesives can be used for the interlayer adhesives 4 A and 4 B. The adhesive sheet 1 may be used for the interlayer adhesives 4 A and 4 B.
[0181] In the optical laminate 10D, the first retardation film 2B is, for example, a half-wave plate in which a liquid crystal material is aligned and fixed. The thickness of the first retardation film 2B is, for example, 5 μm or less, and may be 1 μm or less, or even 0.5 μm or less.
[0182] The second retardation film 2C is, for example, a quarter-wave plate in which a liquid crystal material is aligned and fixed. The thickness of the second retardation film 2C is, for example, 5 μm or less, and may be 1 μm or less, or even 0.5 μm or less.
[0183] In the optical laminate 10D, the adhesive sheet 1 is in contact with the second retardation film 2C. According to the study by the present inventors, when the thickness of the second retardation film 2C in contact with the adhesive sheet 1 is as thin as about 5 μm or less, when the optical laminate 10D is peeled off from an adherend such as an image forming layer, stress tends to concentrate near the second retardation film 2C. In this embodiment, since the adhesive sheet 1 can be easily peeled off from the adherend, even if stress concentrates near the second retardation film 2C, interlayer peeling (for example, interlayer peeling between the interlayer adhesive 4B and the second retardation film 2C) tends not to occur.
[0184] Another example of the optical laminate of this embodiment is shown in Fig. 6. The optical laminate 10E in Fig. 6 has a laminated structure in which a protective film 5, a polarizing film 2A, an interlayer adhesive 4A, a first retardation film 2B, an interlayer adhesive 4B, a second retardation film 2C, an adhesive sheet 1, and a release liner 3 are laminated in this order. After the release liner 3 is peeled off, the optical laminate 10E can be used by being attached to, for example, an image forming layer.
[0185] The protective film 5 has a function of protecting the optical film 2 (polarizing film 2A) which is the outermost layer during distribution and storage of the optical laminate 10E and in a state where the optical laminate 10E is incorporated into an image display device. The protective film 5 may also function as a window to the external space in a state where it is incorporated into an image display device. The protective film 5 is typically a resin film. The resin constituting the protective film 5 is, for example, polyester such as PET, polyolefin such as polyethylene and polypropylene, acrylic, cycloolefin, polyimide, and polyamide, and polyester is preferable. However, the protective film 5 is not limited to the above examples. The protective film 5 may be a glass film or a laminated film including a glass film. The protective film 5 may be subjected to surface treatment such as anti-glare, anti-reflection, and anti-static.
[0186] The protective film 5 may be bonded to the optical film 2 by any pressure-sensitive adhesive. Bonding by a pressure-sensitive adhesive sheet 1 is also possible.
[0187] The optical laminate of this embodiment can be distributed and stored, for example, as a rolled body obtained by rolling up a strip-shaped optical laminate, or as a sheet-shaped optical laminate.
[0188] The optical laminate of the present embodiment is typically used in an image display device, such as a liquid crystal display, an organic EL display, or an inorganic EL display.
[0189] [Characteristics of optical laminates] According to the pressure-sensitive adhesive sheet 1 included in the optical laminate of the present embodiment, the optical laminate tends to be easily peeled off from the adherend. As an example, the optical laminate preferably has an adhesive strength P0 of 10.0 N / 25 mm or less as determined by the following Test 1. Test 1: The optical laminate is attached to non-alkali glass via the adhesive sheet 1 that is 7 days old after preparation. The optical laminate is peeled off from the non-alkali glass at a peeling speed of 300 mm / min and a peeling angle of 90°. The force required for this (adhesive force P0) is measured.
[0190] Specifically, Test 1 is performed by the following method. First, an optical laminate having an adhesive sheet 1 7 days after production is cut into a strip of 150 mm length x 25 mm width to prepare a test piece. Next, the test piece is attached to alkali-free glass via the adhesive sheet 1. The alkali-free glass is glass that does not substantially contain an alkali component (alkali metal oxide), and more specifically, the weight ratio of the alkali component in the glass is, for example, 1000 ppm or less, or even 500 ppm or less. The alkali-free glass is, for example, in the form of a plate, and has a thickness of 0.5 mm or more.
[0191] The test piece is attached to the alkali-free glass using, for example, a rubber roller, so as not to allow air bubbles to be mixed between the alkali-free glass and the adhesive sheet 1. After attaching the test piece, it is left at room temperature (25°C) for 15 minutes to allow the adhesive sheet 1 to adhere to the alkali-free glass. Next, the test piece is peeled off from the alkali-free glass at a peeling speed of 300 mm / min and a peeling angle of 90° (measurement length 80 mm). At this time, the force required to peel the test piece from the alkali-free glass is measured once at intervals of 0.5 s. The average value of the obtained measurements is specified as the adhesive strength P0.
[0192] The adhesive strength P0 is preferably 8.0 N / 25 mm or less, and may be 7.0 N / 25 mm or less, 6.0 N / 25 mm or less, 5.0 N / 25 mm or less, 4.0 N / 25 mm or less, 3.0 N / 25 mm or less, or even 2.0 N / 25 mm or less. The lower limit of the adhesive strength P0 is, for example, 0.5 N / 25 mm or more, and may be 1.0 N / 25 mm or more.
[0193] Furthermore, the optical laminate preferably has an adhesive strength P1 determined by the following Test 2 of 10.0 N / 25 mm or less. Test 2: The optical laminate is attached to non-alkali glass via the adhesive sheet 1 7 days after preparation, and left for 2 hours in an environment of 60°C. The optical laminate is peeled off from the non-alkali glass at a peel speed of 300 mm / min and a peel angle of 90°. The force required for this (adhesive force P1) is measured.
[0194] Test 2 can be performed in the same manner as Test 1, except that the test piece is attached to non-alkali glass and left at room temperature for 15 minutes, and then left in a 60°C environment for a further 2 hours.
[0195] The adhesive strength P1 is preferably 9.0 N / 25 mm or less, and may be 8.0 N / 25 mm or less, 7.0 N / 25 mm or less, 6.0 N / 25 mm or less, or even 5.0 N / 25 mm or less. The lower limit of the adhesive strength P1 is, for example, 1.0 N / 25 mm or more, and may be 3.0 N / 25 mm or more.
[0196] The value (P1-P0) obtained by subtracting the adhesive force P0 from the adhesive force P1 is, for example, 5.0 N / 25 mm or less, 4.0 N / 25 mm or less, or may be 3.0 N / 25 mm or less. The lower limit of the value (P1-P0) is not particularly limited, and is, for example, 0.5 N / 25 mm or more.
[0197] (Embodiment of Image Display Device) An example of the image display device of this embodiment is shown in Fig. 7. The image display device 11 of Fig. 7 has a laminated structure in which a protective film 5, a polarizing film 2A, an interlayer adhesive 4A, a first retardation film 2B, an interlayer adhesive 4B, a second retardation film 2C, an adhesive sheet 1, an image forming layer (e.g., an organic EL layer or a liquid crystal layer) 6, and a substrate 7 are laminated in this order. The image display device 11 has the optical laminates 10B, 10C, 10D, and 10E of Figs. 3 to 6 (excluding the release liner 3). The substrate 7 and the image forming layer 6 may have the same configurations as the substrate and the image forming layer of a known image display device, respectively.
[0198] The image display device 11 in Fig. 7 may be an organic EL display or a liquid crystal display. However, the image display device 11 is not limited to this example. The image display device 11 may be an electroluminescence (EL) display, a plasma display (PD), a field emission display (FED), or the like. The image display device 11 can be used for home appliances, in-vehicle applications, public information displays (PID), and the like.
[0199] The image display device of this embodiment may have any configuration as long as it includes the optical laminate of this embodiment. EXAMPLES
[0200] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the examples shown below.
[0201] <Preparation of polarizing film> [Preparation of polarizer] A long polyvinyl alcohol (PVA) resin film (manufactured by Kuraray, product name "PE3000", thickness 30 μm) was uniaxially stretched in the longitudinal direction (total stretching ratio 5.9 times) using a roll stretching machine, and the resin film was simultaneously subjected to each treatment of swelling, dyeing, crosslinking, washing and drying in order to produce a polarizer with a thickness of 12 μm. In the swelling treatment, the resin film was stretched 2.2 times while being treated with pure water at 20 ° C. In the dyeing treatment, the resin film was stretched 1.4 times while being treated with an aqueous solution at 30 ° C containing iodine and potassium iodide at a weight ratio of 1:7. The iodine concentration in the aqueous solution was adjusted so that the single transmittance of the polarizer to be produced was 45.0%. A two-stage treatment was adopted for the crosslinking treatment. In the first stage of crosslinking treatment, the resin film was stretched 1.2 times while being treated with an aqueous solution at 40 ° C in which boric acid and potassium iodide were dissolved. The aqueous solution used in the first crosslinking treatment had a boric acid content of 5.0% by weight and a potassium iodide content of 3.0% by weight. In the second crosslinking treatment, the resin film was stretched 1.6 times while being treated with an aqueous solution at 65°C in which boric acid and potassium iodide were dissolved. The aqueous solution used in the second crosslinking treatment had a boric acid content of 4.3% by weight and a potassium iodide content of 5.0% by weight. A potassium iodide aqueous solution at 20°C was used for the washing treatment. The potassium iodide content of the aqueous solution used for the washing treatment was 2.6% by weight. The drying treatment was carried out under drying conditions of 70°C and 5 minutes.
[0202] [Preparation of polarizing film] A triacetyl cellulose (TAC) film (Konica Minolta, product name "KC2UA", thickness 25 μm) was attached to each of the main surfaces of the polarizer prepared above using a polyvinyl alcohol-based adhesive. However, the TAC film attached to one of the main surfaces had a hard coat (thickness 7 μm) formed on the main surface opposite the polarizer side. In this way, a polarizing film having a configuration of protective layer with hard coat / polarizer / protective layer (without hard coat) was obtained.
[0203] <Preparation of the first retardation film> A polymerizable liquid crystal material (Paliocolor LC242, manufactured by BASF) exhibiting a nematic liquid crystal phase was prepared as the liquid crystal compound. 10 g of the polymerizable liquid crystal material and 3 g of a corresponding photopolymerization initiator (Irgacure 907, manufactured by BASF) were dissolved in 40 g of toluene to prepare a liquid crystal composition as a coating liquid. Next, the coating liquid was applied to the surface of a PET film, which was a substrate film whose surface had been subjected to an alignment treatment, using a bar coater, and the surface was dried by heating at 90°C for 2 minutes to form a liquid crystal layer. Next, a metal halide lamp was used to irradiate the formed liquid crystal layer with 1 mJ / cm2. 2 The liquid crystal layer was cured to form a first retardation film, which was a liquid crystal alignment solidified layer. The thickness of the first retardation film was 2 μm, and the in-plane retardation Re(550) was 280 nm, that is, the first retardation film formed was a λ / 2 plate.
[0204] <Preparation of the second retardation film> The second retardation film was prepared in the same manner as the first retardation film, except that the coating amount of the coating liquid was adjusted to form a liquid crystal alignment solidified layer having a thickness of 1 μm. The in-plane retardation Re(550) of the second retardation film was 140 nm, that is, the formed second retardation film was a λ / 4 plate.
[0205] <Preparation of circularly polarizing film> [Preparation of UV-curable adhesive composition α] 29.2 parts by weight of hydroxyethyl acrylamide (HEAA), 16.7 parts by weight of 2-acetoacetoxyethyl methacrylate (AAEM), 33.3 parts by weight of acryloylmorpholine (ACMO), 20.8 parts by weight of tripropylene glycol diacrylate (Toa Gosei Co., Ltd., ARONIX M-220) as a crosslinking agent, 3 parts by weight of 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one (BASF, Irgacure 907) as a photopolymerization initiator, and 3 parts by weight of diethylthioxanthone (Nippon Kayaku Co., Ltd., KAYACURE DETX-S) as a radical polymerization initiator were mixed and stirred for 1 hour to prepare an ultraviolet-curable adhesive composition α.
[0206] [Preparation of interlayer adhesive] A monomer mixture containing 79.9 parts by weight of butyl acrylate, 15 parts by weight of benzyl acrylate, 5 parts by weight of acrylic acid, and 0.1 parts by weight of 4-hydroxybutyl acrylate was charged into a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas introduction tube, and a condenser. Next, 0.1 parts by weight of 2,2'-azoisobutyronitrile as a polymerization initiator was added together with ethyl acetate to 100 parts by weight of the monomer mixture, and nitrogen gas was introduced while gently stirring to replace the atmosphere in the flask with nitrogen. The liquid temperature in the flask was kept at about 55°C, and the polymerization reaction was allowed to proceed for 7 hours. Next, ethyl acetate was added to the obtained reaction liquid to adjust the solid concentration to 30% by weight, and a solution of a (meth)acrylic polymer to be used as an interlayer adhesive was obtained. The weight average molecular weight of the obtained polymer was 2.2 million.
[0207] Next, 0.5 parts by weight of trimethylolpropane / tolylene diisocyanate trimer adduct (manufactured by Tosoh, trade name "Coronate L"), 0.1 parts by weight of benzoyl peroxide, which is a peroxide-based crosslinking agent, 0.2 parts by weight of epoxy group-containing silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., trade name "KBM-403"), and 0.5 parts by weight of polyether compound having reactive silyl group (manufactured by Kaneka Corporation, Silyl SAT10) were mixed with the obtained (meth)acrylic polymer solution relative to 100 parts by weight of the solid content of the solution to obtain an adhesive composition to be used for an interlayer adhesive. The prepared adhesive composition was applied to the release surface of a 38 μm-thick polyethylene terephthalate (PET) film (manufactured by Mitsubishi Chemical Polyester Film, MRF38), which is a release film with a silicone treatment applied to the release surface, so that the thickness of the layer after drying was 12 μm, and the mixture was dried at 155 ° C for 1 minute to form an interlayer adhesive.
[0208] [Preparation of circularly polarizing film] A first retardation film (lambda / 2 plate) was attached to the exposed surface of the protective layer (without hard coat) of the polarizing film with ultraviolet-curable adhesive composition α. The attachment was performed as follows. First, the adhesive composition α was applied to the exposed surface of the polarizing film with a coating thickness of 0.5 μm using an MCD coater (manufactured by Fuji Machine Co., Ltd.). Next, the first retardation film was placed on the coating film, and then ultraviolet rays were irradiated from both sides to cure the adhesive composition α. The first retardation film was placed so that the λ / 2 plate was in contact with the coating film. The ultraviolet rays were irradiated using a metal halide lamp with a peak illuminance of 1600 mW / cm. 2 , cumulative dose 1000 / mJ / cm 2 (wavelength 380-440 nm). After completion of the ultraviolet irradiation, hot air drying was performed at 70°C for 3 minutes. Next, the base film used in the preparation of the first retardation film was peeled off from the first retardation film, and an interlayer adhesive was attached to the peeled surface. Next, the film used in the preparation of the interlayer adhesive was peeled off from the interlayer adhesive, and a second retardation film (λ / 4 plate) was attached to the peeled surface. In this way, a circularly polarizing film including a polarizing film, a first retardation film, and a second retardation film was obtained.
[0209] <Preparation of (meth)acrylic polymer A1> A monomer mixture containing 81.9 parts by weight of butyl acrylate (BA), 4.8 parts by weight of acrylic acid (AA), 0.1 parts by weight of 4-hydroxybutyl acrylate (HBA), and 13.2 parts by weight of benzyl acrylate (BzA) was charged into a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser. Furthermore, 0.1 parts by weight of 2,2'-azobisisobutyronitrile (AIBN) was charged as a polymerization initiator together with ethyl acetate for 100 parts by weight of the monomer mixture, and nitrogen gas was introduced while gently stirring to replace the atmosphere with nitrogen. The liquid temperature in the flask was kept at about 55°C and a polymerization reaction was carried out for 7 hours. Thereafter, ethyl acetate was added to the obtained reaction liquid to adjust the solid concentration to 30%, and a solution of (meth)acrylic polymer A1 was obtained.
[0210] <Preparation of (meth)acrylic polymers A2 to A3> Except for changing the monomers and polymerization initiators used as shown in Table 1, solutions of (meth)acrylic polymers A2 to A3 were prepared in the same manner as for (meth)acrylic polymer A1.
[0211] [Table 1]
[0212] The abbreviations in Table 1 are as follows. BA: n-butyl acrylate AA: Acrylic acid HBA: 4-hydroxybutyl acrylate BzA: benzyl acrylate AIBN: Azo polymerization initiator, 2,2'-azobisisobutyronitrile (Kishida Chemical Co., Ltd.)
[0213] Example 1 [Preparation of adhesive composition] A (meth)acrylic polymer, an isocyanate crosslinking agent, a polyhydroxyalkylamine compound, a polyether compound, and the like were mixed so as to obtain the composition shown in Table 2 below, thereby obtaining a solvent-based pressure-sensitive adhesive composition.
[0214] [Preparation of adhesive sheet] The adhesive composition was applied to the surface of a PET film, which was a base film (release liner), so that the thickness of the adhesive sheet after drying would be 20 μm. A fountain coater was used to apply the adhesive composition. The resulting coating film was dried in an air-circulating thermostatic oven at 95° C. for 1 minute to form an adhesive sheet.
[0215] [Preparation of optical laminate] The adhesive sheet thus prepared was transferred from the release film to the second retardation film of the circularly polarizing film and attached to obtain an optical laminate. This optical laminate had the same structure as the optical laminate 10D in FIG.
[0216] (Examples 2 to 26 and Comparative Examples 1 to 23) Except for changing the formulation of the pressure-sensitive adhesive composition as shown in Tables 2 to 4, pressure-sensitive adhesive compositions, pressure-sensitive adhesive sheets, and optical laminates were produced for Examples 2 to 26 and Comparative Examples 1 to 23 by the same method as in Example 1.
[0217] [evaluation] <Weight average molecular weight (Mw) of (meth)acrylic polymer> The weight average molecular weight (Mw) of the obtained (meth)acrylic polymer was measured by GPC (gel permeation chromatography). Analytical equipment: Tosoh HLC-8120GPC Column: Tosoh G7000H XL +GMH XL +GMH XL Column size: 7.8mmφ×30cm each, total 90cm Column temperature: 40℃ ·Flow rate: 0.8ml / min ·Injection volume: 100μl Eluent: Tetrahydrofuran Detector: Differential refractometer (RI) Standard sample: polystyrene
[0218] <Adhesive strength> The adhesive strengths P0 and P1 were measured for the optical laminates of the examples and comparative examples by carrying out the above-mentioned tests 1 and 2. In tests 1 and 2, an alkali-free glass (manufactured by Corning Incorporated, product name "Eagle XG") having a thickness of 0.7 mm was used. The test piece was peeled off from the alkali-free glass using a tensile tester (manufactured by Shimadzu Corporation, autograph SHIMAZU AG-X).
[0219] <Reworkability> The optical laminates of the Examples and Comparative Examples were subjected to the above-mentioned Test 2, and the reworkability was evaluated according to the following criteria. (Evaluation Criteria) A: The optical laminate can be easily peeled off from the non-alkali glass. B: The surface of the optical laminate peeled off from the non-alkali glass is rough, but this does not cause any problems in practical use. C: Interlayer delamination occurs within the optical laminate, and a part of the optical laminate remains on the non-alkali glass.
[0220] <Durability> The optical laminates of the examples and comparative examples were fixed to the surface of alkali-free glass (manufactured by Corning, product name "Eagle XG") having a thickness of 0.7 mm via an adhesive sheet. The optical laminate was fixed in an atmosphere of 23°C and 50% RH. Next, it was treated in an autoclave at 50°C and 5 atm (absolute pressure) for 15 minutes, and then left to cool to 23°C to stabilize the bonding of the optical laminate to the alkali-free glass, and then left in a heated and humidified atmosphere at 60°C and 95% RH for 500 hours. After leaving it, it was returned to an atmosphere of 23°C and 50% RH, and it was visually confirmed whether the optical laminate was peeled off from the alkali-free glass or whether bubbles were generated between the alkali-free glass and the optical laminate, and durability was evaluated according to the following criteria. (Evaluation Criteria) A: No visible changes such as foaming or peeling were observed. B: Separate peeling or slight bubbling is observed at the edge, but is within the range that does not cause any practical problems. C: Significant peeling or foaming is observed at the edge, making it problematic for practical use.
[0221] <Whitening> The degree of whitening of the pressure-sensitive adhesive sheets prepared in the examples and comparative examples was evaluated based on the haze. The haze of the pressure-sensitive adhesive sheet was measured in an atmosphere of 25°C using a haze meter HZ-V3 manufactured by Suga Test Instruments in accordance with JIS K7136:1981. The measurement was performed in a state where four layers of the pressure-sensitive adhesive sheet to be evaluated were attached (total thickness 80 μm) to a slide glass S012140 (thickness 1.3 mm) manufactured by Matsunami Glass Industry Co., Ltd. The measured value V at this time was converted to a value equivalent to a total thickness of 75 μm by the formula: V×75 / 80. (Evaluation Criteria) A: Measured haze is less than 1% B: Measured haze is 1% or more
[0222] <Pot life> The pressure-sensitive adhesive compositions prepared in the Examples and Comparative Examples were left for 6 hours in an environment of 30° C. The viscosity of the pressure-sensitive adhesive composition immediately after preparation and after being left standing was measured, and the pot life was evaluated according to the following criteria. (Evaluation Criteria) A: The viscosity of the pressure-sensitive adhesive composition hardly increases. B: The increase in viscosity of the pressure-sensitive adhesive composition is less than 20P, and is not problematic in practical use. C: The increase in viscosity of the pressure-sensitive adhesive composition is 20P or more.
[0223] <Aging> The adhesive strength P2 of the optical laminates of the Examples and Comparative Examples was determined by the following Test 3. The adhesive strength P2 was compared with the above-mentioned adhesive strength P0, and the rate of progress of the crosslinking reaction in the pressure-sensitive adhesive sheet due to aging was evaluated according to the following criteria. Note that Test 3 was the same as Test 1, except that a pressure-sensitive adhesive sheet 14 days after production was used instead of a pressure-sensitive adhesive sheet 7 days after production. Test 3: The optical laminate is attached to non-alkali glass via an adhesive sheet that has been produced for 14 days. The optical laminate is peeled off from the non-alkali glass at a peel speed of 300 mm / min and a peel angle of 90°. The force required for this (adhesive force P2) is measured. (Evaluation Criteria) A: The value of adhesive strength P2 is almost the same as adhesive strength P0, and the crosslinking reaction in the pressure-sensitive adhesive sheet due to aging is sufficiently fast. B: The value of adhesive strength P2 is significantly different from adhesive strength P0, and the crosslinking reaction in the pressure-sensitive adhesive sheet due to aging is slow.
[0224] [Table 2]
[0225] [Table 3]
[0226] [Table 4]
[0227] The abbreviations in Tables 2 to 4 are as follows. D101E: Trimethylolpropane / tolylene diisocyanate trimer adduct (manufactured by Mitsui Chemicals, product name "Takenate D-101E") EDP-300: N,N,N',N'-tetrakis(2-hydroxypropyl)ethylenediamine (manufactured by ADEKA Corporation, trade name "EDP-300") EDP-450: Polyoxypropylene condensate of ethylenediamine (manufactured by ADEKA Corporation, trade name "EDP-450", molecular weight 450) EDP-1100: Polyoxypropylene condensate of ethylenediamine (manufactured by ADEKA Corporation, trade name "EDP-1100", molecular weight 1100) SAT10: A polyether compound having an alkoxysilyl group (manufactured by Kaneka Corporation, product name "Silyl SAT10") KBM403: 3-glycidoxypropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., product name "KBM-403")
[0228] As can be seen from Tables 2 to 4, the optical laminates of the examples including pressure-sensitive adhesive sheets formed from the pressure-sensitive adhesive composition of the present embodiment had better reworkability than the comparative examples. From these results, it can be said that the pressure-sensitive adhesive composition of the present embodiment is suitable for producing pressure-sensitive adhesive sheets with improved reworkability. Note that, when Test 2 was performed on all of the optical laminates of the comparative examples, interlayer peeling occurred between the interlayer pressure-sensitive adhesive and the second retardation film. [Industrial Applicability]
[0229] The pressure-sensitive adhesive composition of the present invention can be suitably used for producing a pressure-sensitive adhesive sheet equipped in an image display device such as an EL display or a liquid crystal display. [Explanation of symbols]
[0230] 1 Adhesive sheet 2. Optical Film 2A Polarizing Film 2B Retardation film (first retardation film) 2C Retardation film (second retardation film) 10A, 10B, 10C, 10D, 10E Optical laminate 11 Image display devices
Claims
1. A (meth)acrylic polymer (A), an isocyanate-based crosslinking agent in an amount of 2 parts by weight or more based on 100 parts by weight of the (meth)acrylic polymer (A); A polyhydroxyalkylamine compound, A polyether compound, Including, The polyhydroxyalkylamine compound has two or more amino groups, The pressure-sensitive adhesive composition, wherein the polyether compound has a silicon atom and a hydroxyl group and / or a hydrolyzable group bonded to the silicon atom.
2. A (meth)acrylic polymer (A), an isocyanate-based crosslinking agent in an amount of 2 parts by weight or more based on 100 parts by weight of the (meth)acrylic polymer (A); A polyhydroxyalkylamine compound, A polyether compound, Including, The polyhydroxyalkylamine compound is represented by the following formula (1): The pressure-sensitive adhesive composition, wherein the polyether compound has a silicon atom and a hydroxyl group and / or a hydrolyzable group bonded to the silicon atom. 【Chemistry 1】 (In the above formula (1), R 1 , R 2 , R 3 and R 4 are each independently a hydrogen atom or a group represented by the general formula -(R 5 O) m (R 6 O) n In the above general formula, R 5 and R 6 are each independently an alkylene group. 5 The alkylene group of R 6 In the above general formula, m and n are each independently an integer of 0 or more, provided that at least one of m and n is an integer of 1 or more. 1 , R 2 , R 3 and R 4 At least two of the general formula -(R 5 O) m (R 6 O) n In the formula (1), X represents a divalent hydrocarbon group, and p is an integer of 1 or more.
3. 3. The pressure-sensitive adhesive composition according to claim 1, wherein the blending amount of the polyether compound is 0.1 to 5 parts by weight based on 100 parts by weight of the (meth)acrylic polymer (A).
4. The pressure-sensitive adhesive composition according to claim 1 or 2, wherein the polyhydroxyalkylamine compound has a molecular weight of 1,500 or less.
5. 3. The pressure-sensitive adhesive composition according to claim 1, wherein the amount of the polyhydroxyalkylamine compound is 0.01 to 5 parts by weight based on 100 parts by weight of the (meth)acrylic polymer (A).
6. The pressure-sensitive adhesive composition according to claim 1 or 2, wherein the amount of the isocyanate-based crosslinking agent is 13 parts by weight or less based on 100 parts by weight of the (meth)acrylic polymer (A).
7. The pressure-sensitive adhesive composition according to claim 1 , wherein the (meth)acrylic polymer (A) has a structural unit derived from a carboxyl group-containing monomer.
8. The pressure-sensitive adhesive composition according to claim 7 , wherein the (meth)acrylic polymer (A) has a content of the structural unit derived from the carboxyl group-containing monomer of 3 wt % or more.
9. The pressure-sensitive adhesive composition according to claim 1 , wherein the (meth)acrylic polymer (A) has a structural unit derived from an aromatic ring-containing monomer.
10. The pressure-sensitive adhesive composition according to claim 1 or 2, wherein the (meth)acrylic polymer (A) has a weight average molecular weight of 1,000,000 or more.
11. The pressure-sensitive adhesive composition according to claim 1 , wherein the isocyanate-based crosslinking agent is a tolylene diisocyanate-based crosslinking agent.
12. The pressure-sensitive adhesive composition according to claim 1 or 2, further comprising a silane coupling agent.
13. A pressure-sensitive adhesive sheet formed from the pressure-sensitive adhesive composition according to claim 1 or 2.
14. An optical laminate comprising the pressure-sensitive adhesive sheet according to claim 13 and an optical film.
15. The optical laminate according to claim 14 , comprising a polarizing film, a first retardation film, and a second retardation film as the optical films.
16. the pressure-sensitive adhesive sheet is in contact with the second retardation film, The optical laminate according to claim 15, wherein the second retardation film has a thickness of 5 μm or less.
17. An image display device comprising the optical laminate according to claim 14.
Citation Information
Patent Citations
Adhesive composition and adhesive tape or sheet
JP2005179616A
Protection film for polarizing plate, polarizing plate and liquid crystal display apparatus
JP2008096734A